Synthesis, Characterization and Antibacterial Activity of DEAE-C Loaded Cefixime Nano-Particles Against Resistant Bacterial Strains - Muhammad Tayyub Kazam; Saman Arooj; Mahpara Tabassum; Hamid Saeed; Mehwish Iqtedar; Nadeem Ahmad; Muhammad Islam; Muhammad Fawad Rasool; Muhammad Usama; Aleena Maryam (Journal of Pharmaceutical Innovation, 2026)

Molecular networks and signaling pathways governing abiotic stress tolerance in cotton: advances and perspectives - Imran Ullah; Muhammad Nadeem; Hafiz Ghulam Nabi; Nida Shahzad; Zohair Abbas; Isha Shakoor; Diba Kiran; Mehdi Rahimi; Rukhsana Gulab; Rida Batool (Functional & Integrative Genomics, 2026)

Multiplexed CRISPR/Cas9 mediated knockdown of BCH gene in potato enhances beta-carotene to combat vitamin A deficiency - Ujala Nasir; Aneela Yasmeen; Muhammad Awais; Ayesha Latif; Allah Bakhsh; Nadeem Ahmad; Naila Shahid; Saira Azam; Abdul Qayyum Rao; Ahmad Ali Shahid (Plant Science, 2026)

QSPR modeling of anti-COVID drugs using distance-based topological indices - Hafiz Muhammad Fraz; Kashif Ali; Muhammad Faisal Nadeem; Mingqiang Wang; Saurav Mallik (Next Research, 2026)

Projected depletion of high mountain Asia glaciers by 2100: linking mass loss to asynchronous peak runoff - Muhammad Mannan Afzal; Fuming Xie; Yu Zhu; Adeel Ahmad Nadeem; Fazli Hameed; Yi Luo; Tandong Yao; Fubao Sun; Xin Wang; Qiao Liu; Jyoti Karki; Jun Zhou; et al. (Journal of Hydrology, 2026)

Reusing end-of-life reverse osmosis membranes: Strategies, challenges, and future perspectives - Zeeshan Arshad; Muhammad Ashraf; Taha Demraoui; Tauqir Ahmad; Muhammad Bilal Asif; Niaz Ali Khan; Mukarram Zubair; Muhammad Irshad Baig; Nisar Ullah; Yasir Abbas; Almotasembellah Abushaban; Nadeem Baig (Desalination, 2026)

Adaptive strategies of Tamarix aphylla in hyper-saline conditions of Cholistan Desert - Muhammad Akram; Nargis Naz; Hafiz Muhammad Mohsin Hassan; Maqbool Ahmed; Leman Aliyeva; Muhammad Yousaf Nadeem; Hind Saad Alsubaie; Sahar Anwar Almalki; Abdelrahman R. Ahmed; Abdullah R. Alanzi (The Science of Nature, 2026)

Development and Characterization of Exosomes Mediated Transdermal Gel for Enhanced Delivery of Hydroxyurea - Wajeeha Khalid; Rabia Gul; Muhammad Sarfraz; Hamid Bashir; Nadeem Ahmad; Nayab Tahir; Aneela Javed; Muhammad Asad; Ahsan Ibrahim; Aamra Imtiaz; Imran Nazir; Muhammad Imran Amirzada (Journal of Pharmaceutical Innovation, 2026)

Ascorbic and citric acids mitigate cadmium stress and reduce metal accumulation in spinach grown in alkaline calcareous soil - Saira Hameed; Muhammad Nadeem; Muhammad Ashar Ayub; Muhammad Shabaan; Usman Zulfiqar; Hossam S. El-Beltagi; Dilrabo Kodirova; Dilafruz Solieva; Abdumurod Sattarov; Mashael Daghash Alqahtani; Abdulrahman Alasmari (BioMetals, 2026)

Nitrogen stabilizers and crop rotation affect chemical properties and relative abundance of nitrification and denitrification genes in boreal podzolic soils - Irfan Mushtaq; Svetlana Yurgel; Zia-ul Islam; Yeukai Katanda; Muhammad Nadeem; Raymond Thomas; Lakshman Galagedara; Mumtaz Cheema (Science of The Total Environment, 2026)

Dual-loaded chitosan nanocarriers for sustainable management of Pseudomonas syringae in tomato: A critical narrative review and conceptual synthesis - Zeeshan Ahmad; Urooj Farid; Tauqeer Ahmed Qadri; Sana Azeem Kiani; Arslan Ali; Muhammad Nadeem Hassan; Humaira Yasmin (Physiological and Molecular Plant Pathology, 2026)

Nano-microbial suppression of Tribolium castaneum: Mortality, repellency, and enzyme responses to ginger-derived iron oxide nanoparticles and PGPR strains - Aneela Shaheen; Zeeshan Ahmad; Tauqeer Ahmed Qadri; Sidra Batool; Faheem Ahmad; Muhammad Nadeem Hassan; Humaira Yasmin (Journal of Stored Products Research, 2026)

Bridging iron biofortification through integrative strategies from QTL mapping to regulatory-compliant genome editing - Sadia Hakeem; Safia Khushi; Muhammad Hammad Nadeem Tahir; Nadia Hussain Ahmed; Amna Bibi; Zulfiqar Ali (Cereal Research Communications, 2026)
Around two billion people are affected by iron (Fe) malnutrition globally, largely contributed by the consumption of cereal-based diets with low levels of iron and reduced bioavailability due to presence of inhibitor compounds like phenols and phytic acid. Among several methods of enhancing Fe content of staples, genetic biofortification is the most sustainable, and cost-effective method. Genetic biofortification through conventional breeding has succeeded in producing a number of cultivars marketed for high nutrition. However, this approach is limited due to the requirement of large genetic variation, long breeding time, phyto-availability of nutrients through soil only, gene targeting in compatible species only, lack of knowledge of QTL and genetic maps, environmental interactions, risk of linkage drag, and complex interrelations among nutrients as well as with other yield traits. With the advent of genomic approaches for targeted genetic manipulation, transgenic approach offers straightforward and robust techniques to genetically biofortify staples. While transgenic approaches to increasing Fe content have been helpful, genetically modified (GM) cultivars for staple crops may be delayed due to GM regulatory barriers. This chapter reviews the global status of Fe malnutrition, possible solutions to combat its deficiency, and bottlenecks towards Fe biofortification in staples. It also provides insights into transgenic approaches to address this issue as well as way forward to resolve the regulatory issues associated with GM crops by providing alternate options.

Haplotype-based nested association mapping for net form net blotch response in Australian barley - Muhammad Nadeem; Dan Liu; Lisle Snyman; Lee Hickey; Eric Dinglasan (Theoretical and Applied Genetics, 2026)
Key message Haplotype-based nested association mapping conducted in Australian barley identified 30 haploblocks for resistance/susceptibility to net form of net blotch. Stacking multiple resistance haplotypes significantly reduced disease severity. Abstract Net form net blotch (NFNB), caused by Pyrenophora teres f. teres , is a major fungal disease affecting barley, leading to significant yield losses globally. Improving the sustainability of barley production requires identifying genetic sources that confer effective resistance across genetic backgrounds and diverse environments. Considerable progress has been made through mapping studies conducted internationally, but many have largely focused on unadapted germplasm such as landraces or used foreign pathotypes. To support breeding outcomes in Australia, characterization of resistance alleles that are effective against local pathotypes is critical, along with investigating resistances that may already be present in breeding germplasm as this could reduce the time to deployment of resistant cultivars. In this study, we applied the local genomic estimated breeding value approach to perform haplotype mapping using a multi-reference parent nested association mapping (MR-NAM) population developed using resistant breeding lines as donor parents. The population was evaluated across three seasons in Queensland to investigate the genetic architecture of NFNB resistance and genotype-by-environment interactions. We identified 30 haploblocks, with seven representing novel genomic regions not previously associated with NFNB resistance. Three haploblocks on chromosomes 2H, 6H, and 7H were consistently associated with resistance across all environments, suggesting that they likely harbor stable resistance loci. Haplotype stacking analysis demonstrated that combining multiple resistance haplotypes significantly reduced disease severity, with lines carrying 6–10 resistance haplotypes showing progressive improvements in NFNB resistance. The distribution and effectiveness of these key haplotypes across environments, and in diverse genetic backgrounds adapted to Australia (Commander, Compass and La Trobe), highlight the potential to harness them in ongoing pre-breeding and breeding programs.

Foliar application of Ascorbic acid and Gibberellic acid to enhance salinity tolerance in maize crop (Zea mays) - Hira Fatima; Hummera Nawaz; Ameer Khan; Amina Ameer; Muhammad Nadeem; Sohail Abbas (Cereal Research Communications, 2026)

Retraction Note: Matrine alleviates neurobehavioral alterations via modulation of JNK-mediated caspase-3 and BDNF/VEGF signaling in a mouse model of burn injury - Adnan Khan; Bushra Shal; Muhammad Naveed; Bakht Nasir; Nadeem Irshad; Hussain Ali; Salman Khan (Psychopharmacology, 2026)

Engineered Adsorbents for Microplastic Mitigation: From Interfacial Mechanisms to Scalable Environmental Perspectives - Hammad Sajjad; Waleed Altaf; Ramika Javaid; Tehreem Fakhra; Muhammad Hayat; Ammar bin Yousaf; Nadeem Raza; Suryyia Manzoor; Lilia Basilio de Caland (Journal of Environmental Chemical Engineering, 2026)

Modeling groundwater dynamics in a low-lying sedimentary island driven by recharge variability, climate change, and water demand - Muhammad Qasim Mahmood; Xiuquan Wang; Farhan Aziz; Qing Li; Nadeem Tariq (Journal of Hydrology, 2026)

Phosphoric Acid Outperforms Diammonium Phosphate (DAP) in Cadmium Toxicity Alleviation by Decreasing Bioavailability and Optimizing Maize Physiology in Contaminated Alkaline Soil - Nadeem Sarwar; Mujahid; Muhammad Akhtar; Imtiaz Ahmed; Wajid Mahboob; Muhammad Imran Tipu; Muhammad Rashid Shaheen; Mashael Daghash Alqahtani; Usman Zulfiqar (Water, Air, & Soil Pollution, 2026)

Enhancing Phosphorus Availability in Calcareous Soil through Integrated Crop Straw and Mineral Fertilizer Application Under Varied Moisture Regimes - Naila Farooq; Ali Majrashi; Muhammad Ather Nadeem; Tasawer Abbas (Journal of Soil Science and Plant Nutrition, 2026)

Whole Genome Analysis of Propiconazole-Degrading Serratia marcescens BM-Q: A Rhizobacterium - Maha Binte Masood; Muhammad Nadeem Hassan (Current Microbiology, 2026)

Genetic Diversity and Population Structure of 72 Turkish Ficus carica (L.) Genotypes Assessed Using SCoT Markers - Meliha Feryal Sarıkaya; Muhammad Azhar Nadeem; Sarmad Ali Qureshi; Mehmet Bedir; Muhammed Tatar; Amjad Ali; Muhammad Tanveer Altaf; Viyan Acar Uçer; Kağan Kökten; Erdal Aglar; Faheem Shehzad Baloch (Biochemical Genetics, 2026)

Roadside dust as a vector of potentially toxic metals: an ecological and human health risk assessment in urban areas of semi-arid climatic regions - Namoos Khan; Kainat Zarin; Muhammad Adnan; Seemab Akhtar; Irfan Ullah; Javed Nawab; Nadeem Ali (Environmental Monitoring and Assessment, 2026)

Identifying industry 5.0 workforce skills for sustainable and human centric transformation: A multi-stakeholder expert panel study in a developing country - Sabeen Malik; Mehreen Malik; Bibi Khadija; Muhammad Arif Nadeem Saqib (Journal of Environmental Management, 2026)

Retraction notice to “Dual Z-scheme core-shell PANI-CeO2-Fe2O3-NiO heterostructured nanocomposite for dyes remediation under sunlight and bacterial disinfection” [Environ. Res. 215 (2022) 114140] - Faisal Mukhtar; Tauseef Munawar; Muhammad Shahid Nadeem; Muhammad Naveed ur Rehman; Shoukat Alim Khan; Muammer Koc; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Research, 2026)

Retraction notice to “Assessment of hepatotoxicity and nephrotoxicity in Cirrhinus mrigala induced by trypan blue - an azo dye” [Environ. Res. 215 (2022) 114120] - Bilal Hussain; Muhammad Sajad; Hassan Usman; Khalid A. Al-Ghanim; Mian Nadeem Riaz; Aydin Berenjian; Shahid Mahboob; Pau Loke Show (Environmental Research, 2026)

Retraction notice to “Boosted charge separation via Ce2S3 over dual Z-scheme ZnO–Ce2S3–MnO2 core double-shell nanocomposite for the degradation of diverse dye pollutants” [Environ. Res. 251 (2024) 118675] - Tauseef Munawar; Taghrid S. Alomar; Chang-Feng Yan; Saman Fatima; Faisal Mukhtar; Muhammad Shahid Nadeem; Najla AlMasoud; Shoukat Alim Khan; Muammer Koc; Yahya Zakaria; Faisal Iqbal (Environmental Research, 2026)

Investigating thermal performance of PCM-integrated solar windows with multi-discharging modes in a humid subtropical climate - Muzaffar Ali; Ubaid ur Rehman; Nadeem Ahmed Shiekh; Hafiz Muhammad Adeel Hassan; Muhammad Usman; Andrea Ferrantelli; Müslüm Arıcı (Energy and Buildings, 2026)

Efficacy of Vachellia nilotica Extract-coated Urea in Maize: Field Performance and Phytochemical Basis of Urease Inhibition - Rashid Mahmood; Hina Jabeen; Muhammad Ajmal Rana; Faisal Nadeem; Ejaz Ahmed; Muhammad Bilal Chattha (Journal of Soil Science and Plant Nutrition, 2026)

Biopolymer Coated Urea Improves Wheat Productivity and Nitrogen Use Efficiency by Optimizing Plant Physiology and Mineral Acquisition - Wisha Khan; Muhammad Akhtar; Abdul Rasool Awan; Wajid Mahboob; Nadeem Sarwar (Journal of Soil Science and Plant Nutrition, 2026)

Serratia marcescens Isolated from the Cereals of Multi-Copping Systems Mitigate Drought Stress in Wheat (Triticum aestivum. L.) - Madiha Shoukat; Maha binte Masood; Pari Wash; Muhammad Nadeem Hassan (Journal of Crop Health, 2026)

RETRACTED ARTICLE: Modification of a nonlinear transfer-function noise model for the estimation of groundwater recharge - Saad Zaheer; Muhammad Atiq Ur Rehman Tariq; Abdullah Nadeem (Hydrogeology Journal, 2026)

Biochar mediated microbial responses to organic contaminants in soil environments: From mechanisms to ecological implications - Hao Zhu; Sami Ullah; Yuting Xu; Muhammad Salam; Silvia Celletti; Nadeem Iqbal; Muhammad Mohsin Raza; Babar Hussain; Palanisamy Vasudhevan (Applied Soil Ecology, 2026)

Economic Performance of Organic and Conventional Apple Production Systems Under Climate Variability: Evidence from Commercial Orchards - Fatma Mabrouk; Pomi Shahbaz; Ahmed A. Mashaal; Muhammad Nadeem (Applied Fruit Science, 2026)

Green-Synthesized Gold Nanoparticles from Fortunella Margarita (Kumquat) Leaf Extract for Broad-Spectrum Antifungal Control of Postharvest Fruit Crop Pathogens - Bismillah Mubeen; Ammarah Hasnain; Haider Ali; Muhammad Nadeem Khan; Maymoona Saher; Muhammad Umer Iqbal; Syed Atif Hasan Naqvi (Applied Fruit Science, 2026)

Mitigating salinity stress in wheat: employing biochemical parameters and stress tolerance index with foliar application of potassium and salicylic acid - Ilker Ugulu; Zafar Iqbal Khan; Farzana Shaheen; Muhammad Yasin Ashraf; Kafeel Ahmad; Muhammad Nadeem; Asma Ashfaq (Vegetos, 2026)

Computational exploration of Aegle marmelos coumarins: DFT, molecular docking, and dynamics studies for anti-hypertensive activity - Jan Alam; Muhammad Ali Versiani; Nadeem Ahmed; Syed Intasar Husain Taqvi; Syed Tahir Ali; Zaheer Ul-Haq (Natural Product Research, 2026)

A hybrid MDBN-CA framework for simulating urban growth and optimizing multidimensional zoning in sustainable urban planning - Esha Malik; Muhammad Nadeem; Jizong Jiao; Mohammad Arsalan Khan; Abdullah Faiz Al Asmari (Environment, Development and Sustainability, 2026)

Charcoal rot in sesame: infection biology, host resistance mechanism, and genomic-enabled strategies for durable resistance breeding - Amjad Ali; Muhammad Azhar Nadeem; Fatih Ölmez; Cemal Kurt; Faheem Shehzad Baloch (Theoretical and Applied Genetics, 2026)
Sesame ( Sesamum indicum L.) is a globally important oilseed crop, but its production is constrained by charcoal rot, caused by the soil-borne fungus Macrophomina phaseolina. The pathogen’s exceptionally broad host range, long-term soil persistence through microsclerotia, and increased aggressiveness under high temperature and drought make charcoal rot a major destructive constraint in sesame-growing regions. This review integrates current knowledge on the biology, epidemiology, infection processes, and genetic population variability of Macrophomina spp. in relation to charcoal rot development in sesame. We also summarize key host resistance mechanism including pathogen perception, cell wall reinforcement, phenylpropanoid-mediated defense, antioxidant responses, and associated physiological and molecular adaptations. Particular attention is given to the challenges of resistance screening under variable environmental conditions, including heat- and drought-associated disease expression and pathogen diversity, which complicate the identification of stable resistance sources. The review further examines progress in sesame improvement through germplasm characterization, mutation breeding, interspecific introgression, high-throughput phenotyping, and genomic-assisted approaches such as QTL mapping, genome-wide association studies (GWAS), marker-assisted selection, genomic selection, and functional validation. Integrating these tools with multi-omics and gene-editing strategies offers a promising route for accelerating the development of durable, climate-resilient charcoal rot resistance cultivars. Broader use of diverse germplasm, standardized multi-environment phenotyping, and international collaboration will be essential for sustainable resistance breeding and future sesame production.

Usnic acid attenuates inflammation and joint damage in Freund’s complete adjuvant–induced arthritis in rats - Ammara Razaq; Ambreen Ishaque; Muhammad Nadeem Alvi; Emaan Fatima (Inflammopharmacology, 2026)

Statistical optimization of exopolysaccharides by indigenously isolated Lactobacillus strain under submerged fermentation - Madah Zahra Awan; Fouzia Tabssum; Muhammad Nadeem; Najeeb Ullah; Abid Sarwar; Neha Mazhar; Tariq Aziz; Ashwag Shami; Hanan Abdulrahman Sagini; Saleh A. Alsanie; Nouf Abdullah Alharbi; Mansour Albalji (World Journal of Microbiology and Biotechnology, 2026)

Novel design of Fe0-and AC-doped hydroxyapatite-alginate composites for efficient arsenic clean-up: Mechanistic insights from batch and column tests - Behzad Murtaza; Farwah Shamshir; Muhammad Imran; Muhammad Shahid; Kifayat Ullah; Muhammad Nadeem; M. Asif Naeem; Noor Samad Shah; Jianxu Wang; Ajmal Khan; Changseok Han (Journal of Environmental Management, 2026)

Review on flexible frameworks: Phosphazene functional polymers powering the future of membranes - Yasir Abbas; Muhammad Waqar Hameed; Zahid Ali; Ghulam Yasin; Kanwal Shabbir; Ijaz Hussain; Muhammad Ahsan Iqbal; Hafiz M. Adeel Sharif; Zhanpeng Wu; Nadeem Baig; Isam H. Aljundi; Niaz Ali Khan; et al. (Chemical Engineering Journal, 2026)

Integrating CMIP6 climate projections with community-based vulnerability assessment for climate resilience in Haripur, Pakistan - Syed Shujaat Ali; Sabahat Isha; Hamza Paracha; Abdullah Nadeem; Muhammad Atiq Ur Rehman Tariq (Theoretical and Applied Climatology, 2026)

Innovative Approaches to Combat Antimicrobial Resistance: A Review of Emerging Therapies and Technologies - Mujeeb Ur Rahman; Junaid Ali Shah; Muhammad Nadeem Khan; Hazrat Bilal; Daochen Zhu; Zongjun Du; Da-Shuai Mu (Probiotics and Antimicrobial Proteins, 2026)

Gastroprotective effect of Kahweol against ethanol-induced gastric ulcer by employing in silico, in vitro and in vivo approaches - Shahid Khan; Abdul Qadir; Jawad Azam; Muhammad Noman; Nadeem Ahmad; Zaheer Ul-Haq; Kashif Bashir; Tajamul Hussain; Salman Alrokayan; Muhammad Latif; Hussain Ali; Yousaf Kamal; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Legume-based diversified cropping systems increase soil organic carbon labile pools and microbial carbon use efficiency in a 12-year long-term field trial - Muhammad Nadeem Ashraf; Zawar Haider; Muhammad Ahmed Waqas; Zia Ur Rahman Farooqi; Muhammad Sanaullah; Daniel Blackburn; Zhifeng Yan; Munazza Yousra; Ansa Rebi; Allah Nawaz (Journal of Soils and Sediments, 2026)

Formulation and Characterization of Niosomal Suspension of Aloenin for the Treatment of Myocardial Toxicity in Isoproterenol-Induced Rats Via Alteration HO-1/Nrf2/TLR4/ Caspase-3 Signaling Pathways - Samiyah Alshehri; Misbahuddin Rafeeq; Muhammad Afzal; Alaa Hamed Habib; Hadeel A Alsufyani; Samy A Abusikkien; Sami I. Alzarea; Omar Awad Alsaidan; Nadeem Sayyed; Imran Kazmi (Journal of Pharmaceutical Innovation, 2026)

Integrated GC–MS phytochemical analysis and in vivo assessment of antiarthritic activity of Curcuma zedoaria extracts - Yusra Wasti; Syeda Aroosa Mohsin; Muhammad Tahir Aqeel; Sania Atta; Nadeem ul Hassan Khan; Syeda Ayesha Farhana; Humaira Fatima; Iffat Naz (Inflammopharmacology, 2026)

Retraction Note: Trilemma assessment of energy intensity, efficiency, and environmental index: evidence from BRICS countries - Zulifqar Ali Baloch; Qingmei Tan; Nadeem Iqbal; Muhammad Mohsin; Qaiser Abbas; Wasim Iqbal; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2026)

Retraction notice to ‘Source, occurrence, distribution, fate, and implications of microplastic pollutants in freshwater on environment: A critical review and way forward’ [Chemosphere 325 (2023) 138367] - Tonni Agustiono Kurniawan; Ahtisham Haider; Hafiz Muhammad Ahmad; Ayesha Mohyuddin; Hafiz Muhammad Umer Aslam; Sohail Nadeem; Mohsin Javed; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Kit Wayne Chew (Chemosphere, 2026)

Evaluation of Heavy Metal Contamination in Indus Deltaic Creeks Sediments, Sindh, Pakistan: Ecological Risk Assessment and Environmental Implications - Syed Muhammad Rehan Ullah; Syed Muhammad Saqib Nadeem; Sanober Kahkashan; Abdullah; Anwar Zeb (Marine Pollution Bulletin, 2026)

Behavior of piled rafts crossing reverse fault zones: Experimental and numerical evidence for setback strategies - Qipeng Cai; Yan Zhuang; Xiangyu Guo; Muhammad Nadeem; Khalid Elbaz (Soil Dynamics and Earthquake Engineering, 2026)

Green photocatalytic degradation of methylene green dye using oxalic acid and its metal complexes: Mechanistic and predictive insights from ANN, RSM, and DFT studies - Mohammad Tauseef Haider; Rizwan Ashraf; Talib H. Mawat; Faisal Jamil; Adnan Majeed; Anam Shahzadi; Faisal Qaleel; Haris Nadeem; Sabha Khalid; Asma Rehman; Sadia Aziz; Maryam Khalid; et al. (Journal of Water Process Engineering, 2026)

Chitosan-mediated elicitation enhanced production of secondary metabolites and antioxidant assays in callus culture of Ocimum bacilicum L. (Purple Basil) - Gouhar Zaman; Samah Saleh Al-Shybany; Muhammad Naeem Bajwa; Muhammad Salman Khan; Muhammad Nadeem; Muhammad Zia; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Biopolymer Coated Urea Modulates Growth, Physiological and Biochemical Attributes of Maize (Zea Mays L.) Under Drought by Improving Nitrogen and Carbon Acquisition - Nadeem Sarwar; Muhammad Akhtar; Yaosheng Wang (Journal of Soil Science and Plant Nutrition, 2026)

Synergistic Effect of Biochar and Bacillus Subtilis on the Development of Colletotrichum Graminicola in Maize - Nimra Nadeem; Adnan Akhter; Waheed Anwar; Tehmina Anjum; Muhammad Khurshid; Nasir Ali; Sana Javed; Hibba Arshad (Journal of Soil Science and Plant Nutrition, 2026)

Gypsum and Manure Impacts on Contrasting Textured Saline-Sodic Soils and Greenhouse Gas Emissions - Zia Ur Rahman Farooqi; Iftikhar Ahmad; Muhammad Sabir; Aftab Jamal; Ayesha Abdul Qadir; Bryan G. Hopkins; Muhammad Nadeem Ashraf (Journal of Soil Science and Plant Nutrition, 2026)

Is Critical Period for Weed Control Influenced by the Application of Pre-emergence Herbicide in Lentil (Lens culinaris Medik.)? - Muhammad Zia Ul Haq; Anas Ali; Gul Zaib Hassan; Rana Nadeem Abbas; Saira Shafiq; Mubashar Nadeem (International Journal of Plant Production, 2026)

Integrated plant-soil-microbiome responses mediate greenhouse gas emissions in the restoration of a semiarid steppe - Zhen Wang; Xiaojiang Yang; Paul C. Struik; Muhammad Nadeem Ashraf; Carmeron N. Carlyle; Scott X. Chang; Yuanheng Li; Wenbo Zhang; Riliga Wu; Baoming Ji; Ke Jin (Applied Soil Ecology, 2026)

Regulation of biochemical attributes, photosynthetic pigments, and antioxidant activity in Zea mays L. for complete amelioration of heavy metal toxicity using synergistic application of arsenic-tolerant PGPR and nanoparticles - Mohsin Zafar; Humaira Yasmin; Tayyab Shafiq; Rabia Naz; Asia Nosheen; Muhammad Nadeem Hassan (Environmental Science and Pollution Research, 2026)

Remote sensing and multi-method statistical analysis of snow cover variability and hydrological responses in the Upper Indus Basin - Nasir Abbas; Shah Fahd; Ninglian Wang; Muhammad Zubair; Adeel Ahmad Nadeem; Zeeshan Zafar (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Enhanced charge carrier separation in greenly synthesized ZnO-NiO NCs-based Z-scheme heterojunction for photodegradation of ciprofloxacin hydrochloride and hydrogen evolution reaction - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Shoaib Akhtar; Muhammad Shahzad; Akbar Ali; Nadeem Ahmad; Hatem A. Abuelizz; Rashad Al-Salahi (Fuel, 2026)

Functional hydrogels—enabling the gateway for sustainable water treatment and harvesting technologies - Muhammad Shajih Zafar; Marco Vocciante; Johan Bobacka; Muhammad Nadeem Asghar; Muhammad Yousaf; Henrik Grénman (Environmental Research, 2026)

Anti-arthritic and anti-inflammatory effects of BMZD-2CPE in a CFA and carrageenan-induced animal model - Samiullah Wazir; Farah Abid; Aisha Mobashar; Arham Shabbir; Muhammad Awais; Humaira Nadeem; Hafiz Aamir Ali Kharl; Esmael M. Alyami; Amir Bouallegue; Norah Hamdi; Mohammed Bourhia; Abdullah R. Alanzi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Analysis of multiple blockages in a coolant channel of IAEA research reactor using CFD - Muhammad Abdullah; Muhammad Nadeem; Arif; Adnan Hamid (Annals of Nuclear Energy, 2026)

Quantifying key drivers of atmospheric methane across Pakistan using a machine learning approach - Farzana Altaf; Toqeer Muhammad; Shahid Nadeem; Asif Sajjad; Mazhar Iqbal (Environmental Monitoring and Assessment, 2026)

Unveiling the charge transfer pathways in CuWO4/NiFe/SnWO4 coupled S-scheme heterojunction for photocatalytic dye degradation - Rimsha Aqeel; Tanveer Hussain Bokhari; Saqib Javaid; Amina Zafar; Muhammad Inayat Ullah; Muhammad Tariq Nadeem; Atia Khalid; Shafqat Karim; Ting Zhu; Amjad Nisar; Mashkoor Ahmad (Journal of Water Process Engineering, 2026)

Holistic review on Paenibacillus: The multifunctional genus in heavy metal detoxification, pesticide degradation, and abiotic stress mitigation for Sustainable Agriculture - Izhar Khan; Nadeem Ullah; Haris Maqbool; Adnan Hashmi; Basit Khan; Afnan Khalid; Iffat Naz; Najeeba Parre Paker; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Plant and Soil, 2026)

Unravelling the Mechanistic Role of Soil Microbial Interactions in the Suppression of Phytopathogens in Vegetable Agroecosystems of Pakistan - Basit Khan; Nadeem Ullah; Haris Maqbool; Faria Khan; Izhar Khan; Afnan Khalid; Maryam Arshad; Najeeba Parre Paker; Iffat Naz; Muhammad Akmal; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Current Microbiology, 2026)

Evaluation of the preventive effects of turmeric–ginger–oregano supplementation on DMBA-induced breast cancer in Sprague-Dawley rats - Nadeem Anwar; Salma Sultana; Muhammad Ashir Zia (Advances in Traditional Medicine, 2025)

Synergistic effects of selected ethnomedicinal plants with Metronidazole against resistant H. Pylori, and their urease inhibition mechanism - Sania Atta; Marya Nawaz Malik; Muhammad Tahir Aqeel; Iffat Naz; Nadeem Irshad; Sadaf Naz; Nadeem ul Hassan Khan; Faisal Rasheed; Humaira Fatima (South African Journal of Botany, 2025)

Amino acid functionalized graphene oxide nanocomposite with enhanced adsorption capacity towards methyl orange dye: Insights into kinetics and mechanism - Uzaira Jameel; Muhammad Naveed Qasim; Afnan Qabil Alshammari; Naseem Ahmad Khan; Muhammad Mateen; Behzodjon D. Mamatkodirov; Bakhtiyar T. Ibragimov; Xusheng Wang; Muhammad Nadeem Akhtar (Journal of Water Process Engineering, 2025)

Solid phase microextraction of chlorpyrifos residues in food samples using polyacrylamide@MOF/MXene composite - Sumaira Sabir; Nadeem Raza; Muhammad Hayat; Suryyia Manzoor; Faryal Aftab; Lilia Basilio de Caland; Muhammad Imran Khan; Ahmed Yar; Faisal K. Algethami; Mostafa E. Salem; Anis Ahmad Chaudhary; Muhammad Naeem Ashiq (Food Chemistry, 2025)

Investigation of N-desmethyl-acetamiprid-induced neurotransmitter disturbances in cerebrospinal fluid from leukemia patients - Mengya Si; Muhammad Nadeem Khan; Hazrat Bilal; Muhammad Shafiq; Sabir Khan; Xiaoling Guo; Meimei Wang; Jilong Wu; Wang Zhen; Fen Yao; Adela Jing Li; Xiaoyang Jiao (Environmental Toxicology and Pharmacology, 2025)

Collateral damage of neonicotinoid insecticides: Unintended effects on gut microbiota of non-target organisms - Muhammad Nadeem Khan; Hazrat Bilal; Sabir Khan; Muhammad Shafiq; Xiaoyang Jiao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Synergistic Sustainable Strategies for Microplastic Pollution Eradication by Hedgehog − Shaped Polyoxometalate − Ionic Liquids Supported Magnetic Biochar - Hameed Ullah; Tahani Rahil Aldhafeeri; Inas A. Ahmed; Khurram Shahzad Munawar; Shahid Hussain; Nadeem Nawaz; Uzma Saleem; Muhammad Sohail; Hafiz Muhammad Asif (Water, Air, & Soil Pollution, 2025)

Toxic Metals in the Workplace: Assessing Heavy Metal Contaminants in Indoor Dust of Auto Parts Stores and Their Impact on Health of Employees - Nadeem Ali; Sultan H. Alamri; Jahan Zeb; Mohammad Rehan; Nisreen Rajeh; Nabil Alhakamy; Mohamed I. Orif; Muhammad Imtiaz Rashid; Syed Ali Musstjab Akber Shah Eqani; Hani Z. Asfour (Water, Air, & Soil Pollution, 2025)

Unveiling genetic diversity and population structure in lentil (Lens culinaris) germplasm through scot markers - Sarmad Ali Qureshi; Muhammad Azhar Nadeem; Meliha Feryal Sarıkaya; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altafl; Dilek Tekdal; Muhammad Kashif Ilyas; Seyithan Seydoşoğşu; Sezai Ercişli; Kağan Kökten; Faheem Shahzad Baloch (Molecular Biology Reports, 2025)

Understanding the role of Hedgehog signaling pathway and gut dysbiosis in fueling liver cancer - Naz Fatima; Hooriya Fatima; Sadia Ahmad; Muhammad Abu Talha Safdar Hashmi; Nadeem Sheikh (Molecular Biology Reports, 2025)

Unveiling the Potential of Garcinia Atroviridis Root-Derived Phenolic Compounds Against Breast Cancer: Isolation, Network Pharmacology and In-Silico Approaches - Nur Salsabila Binti Ahmad Roslan; Miah Roney; Abdul Rashid Issahaku; Md. Nazim Uddin; Mohd Fadhlizil Fasihi Mohd Aluwi; Seema Zareen; Anke Wilhelm; Ahmad Mahfuz Gazali; Muhammad Nadeem Akhtar; Normaiza Binti Zamri (Journal of Pharmaceutical Innovation, 2025)

Prediction of RNA editing sites and genome-wide characterization and identification of PERK gene family in Oryza sativa in response to salinity stress - Hafiz Muhammad Waqas; Muhammad Abu Bakar Saddique; Sajid Fiaz; Afnan A. Alnufaei; Muhammad Ali Sher; Badr Alharthi; Muhammad Hammad Nadeem Tahir; Mahmood Alam Khan; Shahmeer Shahid; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2025)

Probiotic characteristics and survival of a multi-strain lactic acid bacteria consortium in simulated gut model - Muhammad Nadeem Khan; Saeeda Bashir; Afifa Afzal; Naghmana Andleeb; Lukasz Krych; Dennis Sandris Nielsen; Muhammad Imran (Folia Microbiologica, 2025)

Predictive modelling of radon variations in time series using wavelets, multiple linear regression and ARIMA - Nadeem Bashir; Awais Rasheed; Muhammad Osama; Adil Aslam Mir; Muhammad Rafique; Saeed Ur Rahman; Dimitrios Nikolopoulos; Muhammad Abdul Basit; Aftab Alam; Aleem Dad Khan Tareen; Kimberlee Jane Kearfott (Isotopes in Environmental and Health Studies, 2025)

Biochemical and comparative genome analysis of Bacillus velezensis HU-91 imparting drought stress tolerance in wheat (Triticum aestivum L.) - Pari Wash; Saqib Mumtaz; Muhammad Nadeem Hassan (South African Journal of Botany, 2025)

Recent advancements in UiO-66(Zr) MOFs and their derivatives: Designing water-stable membranes for water applications - Yahaya A. Muhammad; Muhammad Sajid; Abubakar Umar; Niaz Ali Khan; Ismail Abdulazeez; Billel Salhi; Nadeem Baig; Wail Falath (Desalination, 2025)

A machine learning assisted approach to classify rose species and varieties with laser induced breakdown spectroscopy - Maryam Manzoor; Muhammad Faheem; Muhammad Nadeem; Guljan Shreen; Faisal Hayat; Adnan Younis; Yasir Jamil (Analytica Chimica Acta, 2025)

Evaluation of repellent and contact toxic effects of Citrullus colocynthis against the Periplaneta americana - Adeena Malik; Khalid Mehmood; Muhammad Sajid Nadeem (International Journal of Tropical Insect Science, 2025)

Offshore wind resource assessment and 7E analysis of offshore wind farms on the coastal belt of Pakistan - Talha Bin Nadeem; Asad A. Naqvi; Muhammad Saad; Kinza Malik; Ahsan Ahmed (Process Safety and Environmental Protection, 2025)

Native plantations foster phylogenetic cohesion while nonnative plantations promote higher species turnover in understory vegetation in subtropical managed forest - Shoaib Ilyas; Sehrish Sadia; Mr Nadeem; Abeer Al-Andal; Asma Jabeen; Fahim Arshad; Sanaullah Sattar; Zarafshan Abbas; Muhammad Waheed (Journal of Environmental Management, 2025)

Precipitation of rare earth phosphates through apatite leach as by-product of nitrophos acid from unconventional phosphate deposit of carbonatite, Malakand, Pakistan - Farva Arshad; Munirah Atique Khan; Attiqa Nasir; Muhammad Haider Ali; Lubna Basit; Muhammad Nasir Siddique; Muhammad Nadeem (Hydrometallurgy, 2025)

Effect of erucic acid against DMBA-induced breast cancer via inflammatory/apoptosis pathway - Abdulaziz Alamri; Fahad A. Al-Abbasi; Muhammad Afzal; May M. Alqurashi; Thamir M. Eid; Hayat M. Albishi; Ehssan Moglad; Nadeem Sayyed; Imran Kazmi (Food Bioscience, 2025)

AI-powered optimization of reactive red 195 dye decolorization: Evaluating the impact of operational factors - Zubair Khaliq; Anum Javaid; Abdulaziz Bentalib; Muhammad Bilal Qadir; Zubera Naseem; Shumaila Kiran; Fayyaz Ahmad; Nimra Nadeem; Maryam Bibi (Desalination, 2025)

Effects of chlorophenols on microbial activity and functional diversity: Recent advances in OMICs approaches and soil microbial remediation - Nadeem Iqbal; Muhammad Nauman; Babar Hussain; Sami Ullah; Palanisamy Vasudhevan; Dil Khurram; Riyazuddin Riyazuddin; Shengyan Pu (Applied Soil Ecology, 2025)

Sustainable Fruit Production: Enhancing Technical Efficiency and Climate Resilience in Apple Orchards - Yi Wang; Abida Hafeez; Pomi Shahbaz; Shamsheer ul Haq; Muhammad Nadeem (Applied Fruit Science, 2025)

Predicting ambient PM2.5 levels in the Yangtze River Delta with random forest algorithms: A machine learning approach - Ahmad Hasnain; Muhammad Zaffar Hashmi; Uzair Aslam Bhatti; Basit Nadeem; Geng Wei; Waqas Akram Cheema; Muhammad Asif (Environment, Development and Sustainability, 2025)

Molecular screening of stripe rust and powdery mildew resistance genes in European bread wheat using the validated gene-specific SSR markers - Rada Šućur; Amjad Ali; Parnaz Mortazavi; Velimir Mladenov; Bojan Jocković; Jin Ying Gou; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Yong Suk Chung (Physiological and Molecular Plant Pathology, 2025)

Development of empirical models for forecasting of global solar radiations for different climatic regions of Pakistan - Talha Bin Nadeem; Yousuf Baig; Muhammad Talha Ansari (Next Research, 2025)

Enhancing seismic activity classification in augmented soil gas radon time series data through computational intelligence techniques - Nadeem Bashir; Adil Aslam Mir; Muhammad Osama; Saba Maqsood Abbasi; Dimitrios Nikolopoulos; Shahzad Ahmad Qureshi; Muhammad Rafique (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Corrigendum to “AI-powered optimization of reactive red 195 dye decolorization: Evaluating the impact of operational factors” [Desal. Volume 612 (2025), article number: 118936 https://doi.org/10.1016/j.desal.2025.118936] - Zubair Khaliq; Anum Javaid; Abdulaziz Bentalib; Muhammad Bilal Qadir; Zubera Naseem; Shumaila Kiran; Fayyaz Ahmad; Nimra Nadeem; Maryam Bibi (Desalination, 2025)

Synergizing ZIF-67 activity with polyetherimide to achieve dendrite and shuttle-free lithium sulfur batteries - Waseem Raza; Andleeb Mehmood; Arshad Hussain; Karma M. Albalawi; Munir Ahmad; Muhammad Ahmed; Manal S. Ebaid; Muhammad Asim Mushtaq; Nadeem Raza; Huayu Huang; Lihong Ao; Dongqing Liu; et al. (Chemical Engineering Journal, 2025)

Phycocyanin as a sustainable future resource: A review on recent advancements, fundamental challenges, opportunities and applications - Haider Ali; Rashid Iftikhar; Muhammad Ali Inam; Muhammad Umer Abbas; Sahar Saleem; Faras Ahmad Shahbaz; Humayun Nadeem; Aleena Tahir; M. Momin (Bioresource Technology Reports, 2025)

Biochemical validation for the therapeutic use of Plumeria rubra in coagulation disorders: a study combining in silico, in vitro, and in vivo approaches - Imran Ahmad Khan; Muhammad Anwar; Sarmad Frogh Arshad; Athar Hussain; Muhammad Usman; Mohammed Nadeem Ansari; Hasan Junaid Arshad; Asma Shah Rukh; Qurat Ul Ain; Maliha Khalid Khan (Protoplasma, 2025)

GC-MS profiling and biological investigations of Cissampelos pareira L. & Lantana camara L. - Muhammad Wasim; Hafiz Abdul Rafey; Sadia Sarwar; Humaira Nadeem; Samir Anis Ross; Farhat Shaheen (Natural Product Research, 2025)

Development and characterisation of buccal dispersible film, syrup and effervescent granules of extemporaneous antigout remedy - Ayisha Shaukat; Khalid Hussain; Naureen Shehzadi; Muhammad Tanveer Khan; Siddiqa Perveen; Nadeem Irfan Bukhari (Natural Product Research, 2025)

Cadmium and zinc inflows through wastewater irrigation govern soil metal balances in wheat-sorghum cropping system - Ayta Umar; Muhammad Nadeem; Shahid Hussain (Environmental Monitoring and Assessment, 2025)

Correction to: Transition metal-doped SnO2 and graphene oxide (GO) supported nanocomposites as efficient photocatalysts and antibacterial agents - Tauseef Munawar; Muhammad Shahid Nadeem; Faisal Mukhtar; Muhammad Naveed ur Rehman; Muhammad Riaz; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Science and Pollution Research, 2025)

Impact Analysis of Climate Change, Socioeconomic Development, and Hydropower Generation on Water Availability in the Chitral River Basin Using Water Evaluation and Planning (WEAP) Model - Bushra Zaman; Muhammad Atiq Ur Rehman Tariq; Abdullah Nadeem; Muhammad Kaleem Sarwar; Muhammad Waseem; Mudassar Iqbal; Shakeel Hayat; Khalil Ahmed; Muhammad Usman (Water Conservation Science and Engineering, 2025)
Water, energy, and food are three major issues of concern because of the rapid growth of the population and economy, which are exacerbated by climate change. The disparity between the availability and demand of water is largely driven by domestic and agricultural uses, and it is important to evaluate its impact on hydropower generation. This study aims to integrate climate change, socioeconomic development, and hydropower generation analysis using the water evaluation and planning model (WEAP). This study uses the CMIP6 model to make future projections under shared socioeconomic pathways (SSPs). This study examined the projections of water demand under different scenarios (SSP1-2.6, SSP2-4.5, and SSP5-8.5) using the MPI-ESM1-2HR climate change model. In the reference year 2000, domestic water demand stood at 15 MCM, escalating to 54 MCM under the SSP5-8.5 scenario. Concurrently, agricultural water demand, which was 93.72 MCM in 2000, is projected to surge to 197.35 MCM by 2050. Based on expected future changes in streamflow, the results show that Golen Gol’s hydropower potential varies with the effects of socioeconomic and climatic changes. However, the fluctuation in hydropower generation is more prominent during June and July, leading to an increase in hydropower in future scenarios. The study findings suggest that by 2050, the combination of population growth and agricultural expansion will substantially escalate water demand, posing risks to both the environment and human populations. Consequently, adopting enhanced irrigation methods, refining agricultural techniques, and erecting water conservation and retention infrastructures could effectively mitigate these challenges. To formulate sustainable water management strategies, it is advised to further utilize the integrated water–energy–food nexus approach, strengthened by merging WEAP with the energy modeling program Low Emissions Analysis Platform (LEAP) for hydropower generation.

Effect of sakuranetin against cyclophosphamide-induced immunodeficiency mice: role of IFN-γ/TNF-α/IgG/IgM/interleukins - Khalid Saad Alharbi; Sattam Khulaif Alenezi; Tariq Alsahli; Muhammad Afzal; Mohammad Jaffar Sadiq Mantargi; Imran Kazmi; Nadeem Sayyed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Synthesis, biological evaluation, and in silico studies of chalcone-based ketamine derivatives with preferential COX-2 inhibitory activity - Syed Muzzammil Masaud; Humaira Nadeem; Abida Shamim; Muhammad Kazim Zargaham; Usman Shareef; Sana Ayaz; Babar Murtaza (Medicinal Chemistry Research, 2025)

New AI explained and validated deep learning approaches to accurately predict diabetes - Ifra Shaheen; Nadeem Javaid; Nabil Alrajeh; Yousra Asim; Syed Muhammad Abrar Akber (Medical & Biological Engineering & Computing, 2025)

Proline-Induced Changes in Cellular Redox Balance by Modulating Photosystem-II, Photosystem-I, and Activities of Antioxidants in Bread Wheat (Triticum aestivum L.) Under Salinity Stress - Ayesha Khalid; Sarah Ambreen; Aneela Kanwal Shahzadi; Nadeem Hussain; Azra Manzoor; Habib-ur-Rehman Athar; Zafar Ullah Zafar; Muhammad Ashraf (Journal of Plant Growth Regulation, 2025)

Evaluation of Aqueous Extracts of Some Medicinal Plants Against the Wild Radish—an Eco-Friendly Aproach to Control the Troublesome Weed - Muhammad Asaud Islam; Rizwan Maqbool; Abdul Khaliq; Muhammad Ather Nadeem; Muhammad Yaseen (Journal of Crop Health, 2025)

Exploring the antitumor effects of Pd(II) complexes with nitrogen donor ligands towards breast carcinoma - Shazia Hussain; Sara Masood; Shabeeb Hussain; Irfan Hussain; Fouzia Malik; Muhammad Nadeem Akhtar; M. Naveed Zafar (BioMetals, 2025)

Navigating soil microbiota shifts to organic pollutants: Insights into the roles of nZVI-biochar in soil ecosystem restoration - Sami Ullah; Babar Hussain; Nadeem Iqbal; Muhammad Salam; Muhammad Mohsin Raza; Shengyan Pu (Applied Soil Ecology, 2025)

Translational potential of GADD45α: biomarker and therapeutic target in age-associated neurodegeneration and longevity - Imran Kazmi; Fahad A. Al-Abbasi; Mustafa Zeyadi; Misbahuddin Rafeeq; Alaa Hamed Habib; Johar Iqbal; Sami I. Alzarea; Omar Awad Alsaidan; Muhammad Shahid Nadeem (Biogerontology, 2025)

Platelet-Rich Plasma (PRP) Mitigates Kidney Dysfunction in Alloxan-Induced Diabetic Mice via Modulation of Renal Iron Regulatory Genes - Humaira Allay Ali; Muddasir Hassan Abbasi; Tasleem Akhtar; Amin Arif; Mehreen Anjum; Sana Fatima; Rabia Mehmood; Adil Farooq; Nadeem Sheikh; Muhammad Babar Khawar (Biochemical Genetics, 2025)

Rapid synthesis of charged covalent organic framework for sustainable reverse osmosis membranes - Umar H. Nuhu; Niaz Ali Khan; Ijaz Hussain; Mengying Long; Billel Salhi; Nadeem Baig; Ismail Abdulazeez; Khan Alam; Sikandar Khan; Muhammad Usman; Umer Zahid; Isam H. Aljundi (Desalination, 2025)

Subsurface placement of controlled-release blended fertilizers mitigates ammonia volatilization by promoting nitrogen transformation in rice fields - Sajjad Ahmad; Muhammad Yousaf Nadeem; Shen Gao; Quanxin Li; Yanfeng Ding; Zhenghui Liu; Yu Jiang; Weiwei Li; Ganghua Li (Agriculture, Ecosystems & Environment, 2025)

Turn-On-Fluorescence Sensor and Solid Sensory Chip for Cyanide Detection - Muhammad Zahid; Nadeem Raza; Samuel Bonne; Mostafa E. Salem; Negin G. Niksirat; Muhammad Zeshan; Muhammad Rafiq; Jian Zhang; Muhammad Saleem (Journal of Fluorescence, 2025)

Recombinant production and characterization of novel carboxypeptidase from thermophilic archaeon Thermococcus siculi - Saima Iftikhar; Maida Wahid; Muhammad Shahid Nadeem; Farheen Aslam; Khushi Muhammad (Biologia, 2025)

Spatio-temporal distribution, diet and human conflict of snow leopard (Panthera uncia) in the Khunjerab National Park, Gilgit Baltistan - Saira Akber; Tariq Mahmood; Tahir Mehmood; Amjad Rashid Kayani; Muhammad Sajid Nadeem; Faraz Akrim (Food Webs, 2025)

Exploring the Role of Plant Growth-Promoting Bacteria in Biodegradation of Plastic: A Review - Haris Maqbool; Fazal Ur Rehman; Izhar Khan; Nadeem Ullah; Muhammad Anwar Sajad; Nazir Mohammad; Maria Kalsoom; Shafiq Ur Rehman; Muhammad Farooq Hussain Munis; Malka Saba; Hassan Javed Chaudhary (Water, Air, & Soil Pollution, 2025)

Exogenous Application of Nitrogen (N) and Potassium (K) Improves Drought Tolerance in Plants: A Review - Saira Sulaman; Muhammad Nadeem; Muhammad Shabaan; Sule Orman; Muhammad Anwar-ul-Haq; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2025)
With rising climate anomalies and deterioration of ecological balance, water shortage has emerged as a major environmental problem faced by mankind, which has considerably limited agricultural productivity worldwide. Drought stress generates an insidious hazard by destabilizing global hydrological cycle and due to its increased frequency, severity and associated adverse impacts on climate conditions, drought has obtained attention world over. Exposure to severe and acute drought stress disturbs physiological functioning of plants and inhibits the efficiency of photosynthetic system. As a result, lesser photosynthate production causes lower plant biomass and yield. Hence, it is imperative to sustain and improve plant growth and productivity under water shortage conditions to minimize its dreadful impacts. Current review summarizes the adverse impacts of drought stress on various agricultural crops, its alleviation strategies and various adaptations encountered by plants under drought stress. More importantly, current review emphasizes the beneficial roles played by macronutrients such as nitrogen (N) and potassium (K) in alleviating the adverse impacts of drought stress. As these essential nutrients have reportedly been involved in alleviating the negative impacts of drought stress on plant growth and therefore, major information in the current review article revolves around the N and K supply to the plant under drought stress. In addition, current review necessitates the use of optimum doses of N and K fertilizers to ensure maximum resource utilization efficiency and increased drought resilience.

Nano Zinc Oxide Enhances Corn Growth and Nutrient Uptake: Comparison between Soil Drench and Seed Coating Applications in Alkaline Sandy Soils - Wiqar Ahmad; Jaya Nepal; Xiaoping Xin; Muhammad Nadeem; Zhenli He (Journal of Soil Science and Plant Nutrition, 2025)

Hydropriming and Nano-Priming with Zinc and Iron Oxide Nanoparticles Improved Growth and Physio‑Biochemical Attributes of Sugarcane (Saccharum officinarum L.) Propagated Through Bud Nodes - Rafi Qamar; Syed Nasir Abbas; Atique-ur-Rehman; Hafiz Muhammad Rashad Javeed; Muhammad Ather Nadeem; Muhammad Ehsan Safdar; Muhammad Yaseen; Arkadiusz Artyszak; Mona S. Alwahibi; Manal Abdulaziz Binobead (Journal of Soil Science and Plant Nutrition, 2025)

Correction: Combined Effects of Reduced Tillage and Strip Intercropping on Soil Carbon Sequestration in Semi-Arid Environment - Sana ur Rehman; Shahzada Sohail Ijaz; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Muhammad Ansar; Shroz Fatima; Ayesha Siddiqa; Muhammad Nadeem Ashraf; Imran Haider; Muhammad Bilawal Junaid; Muhammad Ali Raza; Haishui Yang (Journal of Soil Science and Plant Nutrition, 2025)

Combined Effects of Reduced Tillage and Strip Intercropping on Soil Carbon Sequestration in Semi-Arid Environment - Sana ur Rehman; Shahzada Sohail Ijaz; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Muhammad Ansar; Shroz Fatima; Ayesha Siddiqa; Muhammad Nadeem Ashraf; Imran Haider; Muhammad Bilawal Junaid; Muhammad Ali Raza; Haishui Yang (Journal of Soil Science and Plant Nutrition, 2025)

Mitigating the Greenhouse Gases Intensity and Improving Fine Rice Productivity with Coated Urea Fertilizers in Semi-Arid Conditions - Ayesha Mustafa; Imran Khan; Muhammad Umer Chattha; Hafiz Abdul Wahab; Faisal Nadeem; Rikza Awan; Uthman Balgith Algopishi; Mohamed Hashem; Muhammad Umair Hassan (Journal of Soil Science and Plant Nutrition, 2025)

Exploring genetic diversity of Turkish fig (Ficus carica L.) germplasm using inter-Primer Binding Site (iPBS) retrotransposon markers - Viyan Acar Uçer; Erdal Aglar; Parnaz Mortazavi; Sarmad Ali Qureshi; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altaf; Mehmet Bedir; Sezai Ercişli; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Application of leaf water content measurement to improve herbicide efficacy for effective weed management in a changing climate – A review - Tasawer Abbas; Naila Farooq; Muhammad Ather Nadeem (Crop Protection, 2025)

Evaluation of cotton (Gossypium hirsutum L.) seed longevity and deterioration: Physiological and biochemical aspects in relation to moisture contents during storage in different module systems - Faryal Fatima; Ehsan Khalid; Irfan Afzal; Muhammad Usman; Muhammad Ather Nadeem; Muhammad Kamran (Journal of Stored Products Research, 2025)

Enhancing food security: machine learning-based wheat yield prediction using remote sensing and climate data in Pakistan - Nadeem Ahmed; Syed Amer Mahmood; Muhammad Haseeb; Zainab Tahir; Saira Batool (Theoretical and Applied Climatology, 2025)

Assessment of water quality and occurrence of multidrug-resistant clinically relevant bacteria in drinking water in the twin cities of Pakistan - Nudrat Nadeem; Muhammad Nadeem; Nazish Bostan; Sadia Sattar; Roger Simm; Sundus Javed (Environmental Monitoring and Assessment, 2025)
Water filtration plants are a main source of drinking water for local populations in almost all big cities of Pakistan but these filtration plants are ineffective in eliminating contaminants from water. This study was conducted to evaluate water quality with specific focus on physicochemical parameters and bacterial contamination including occurrence of multidrug-resistant bacteria in drinking water collected from filtration plants ( N = 64) of the twin cities of Pakistan. Physicochemical parameters were analyzed following American Public Health Association standard guidelines and total coliform count was determined using membrane filtration method. Gram-negative bacteria were isolated and characterized in terms of species and antibiotic susceptibility. Elevated levels of total dissolved solids, nitrates, total coliforms, lead and copper were found in several samples. Multivariate correlation coefficient revealed significant positive correlation between nitrate levels and total coliform count in bacteriologically contaminated samples. Antibiotic resistance patterns revealed multidrug-resistant and extensively drug-resistant bacteria with high resistance against third generation cephalosporins. Our results highlight the urgent need for improved water filtration processes and regular monitoring to provide safe drinking water to the local community.

Manipulating electron shuttling in photo fermentative biohydrogen production from lignocellulosic biomass through engineered Z-scheme photo nanocatalysts - Muhammad Usman; Faiqa Nadeem; Farzana Jabeen; Muneeb Ur Rahman; Hina Ramzan; Muhammad Shahzaib; Zhiping Zhang; Nadeem Tahir (Chemical Engineering Journal, 2025)

Safety assessment of novel oxadiazole derivatives in acute and sub-acute toxicity studies - Syeda Rida Zainab; Jehan Zeb Khan; Humaira Nadeem; Muhammad Khalid Tipu; Nadeem Irshad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Mineral profiling of Turkish wheat genetic resources unveiled their conserved potential for biofortification in combating hidden hunger - Husnu Aktaş; Muhammad Azhar Nadeem; Yusuf Tutuş; Serap Doğan; Mehmet Karaman; İrfan Erdemci; Meng-Lu Wang; Jin-Ying Gou; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Highly efficient phosphate extraction from water using bio-composites of nano zero valent iron supported on orange peel powder (nZVI@OPP): performance evaluation and mechanistic insights - Fahad Nadeem; Muhammad Ali Inam; Rashid Iftikhar; Safi Ullah Gill; Hira Amjad (Environmental Science and Pollution Research, 2025)

Long-term grass lawn management increases soil organic carbon sequestration and microbial carbon use efficiency - Muhammad Nadeem Ashraf; Irfa Mehmood; Zia Ur Rahman Farooqi; Muhammad Itazaz Hassan; Muhammad Sanaullah; Muhammad Mubashar Zafar; Khalid M. Elhindi (Environmental Monitoring and Assessment, 2025)

Retraction Note: Evaluation of toxicity potential of cobalt in wheat irrigated with wastewater: health risk implications for public - Fu Chen; Zafar Iqbal Khan; Asma Zafar; Jing Ma; Muhammad Nadeem; Kafeel Ahmad; Shehzadi Mahpara; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; et al. (Environmental Science and Pollution Research, 2025)

Molecular screening of diverse Tomato germplasm for root-knot nematode resistance using the Mi23 marker - Parnaz Mortazavi; Amjad Ali; Muhammed Tatar; Fatih Ölmez; Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Hayriye Yildiz Dasgan; Boran Ikiz; Tuğçe Temtek; Ömer Faruk Bilgin; Ayşe Mücahitoğlu; Mahmut Bayram; et al. (Physiological and Molecular Plant Pathology, 2025)

Enhanced charge transferring through defects-mediated metal‑carbon nanocomposites for efficient dye degradation under visible light - Muneeb Ur Rahman; Faiqa Nadeem; Muhammad Usman; Muhammad Shahzaib; Hina Ramzan; Nimra Nadeem; Zhiping Zhang; Nadeem Tahir (Journal of Water Process Engineering, 2025)

Utilization of locally sourced waste fats for biodiesel production: Experimental characterization and environmental life cycle assessment - Muhammad Aqil Khan; Nadeem Ahmed Sheikh; Khan Zaib Jadoon; Abubakr Ayub; Tabbi Wilberforce Awotwe; Rasikh Tariq (Biomass and Bioenergy, 2025)

Molecular diversity and phylogenetic analysis of ten sheep breeds from Khyber Pakhtunkhwa, Pakistan, based on mitochondrial D-loop sequences - Shabir Ahmed; Muhammad Shahid Nadeem; Anna M. Johansson; Elisabeth Jonas; Khushi Muhammad; Sardar Azhar Mehmood (Mammalian Genome, 2025)

Exploring the therapeutic potential of Ixora extract: a comprehensive review of mediated studies - Rabiyah Nadeem; Muhammad Imran; Zohaib Saeed; Muhammad Pervaiz; Umer Younas (Advances in Traditional Medicine, 2025)

Identification and quantification of selected heavy metals by ICP-OES in skin whitening creams marketed in Pakistan - Mirza Nadeem Ahmad; Umm-e-Khadija Ashraf; Muhammad Naveed Anjum; Shumaila Kiran; Shazia Abrar; Muhammad Fayyaz Farid (Environmental Monitoring and Assessment, 2025)

Progress on synthesis, characterization and photocatalytic applications of bismuth oxyhalide based nanomaterials in cleaner environment and energy - A review - Mehwish Tabassum; Aima-tul-ayesha; Bin Yang; Xin Jia; Muhammad Nadeem Zafar (Journal of Cleaner Production, 2025)

Amine-functionalized organically modified silica for the effective adsorption of Chlorpyrifos and Triazophos Residues from Orange juice - Muhammad Hayat; Suryyia Manzoor; Nadeem Raza; Hina Raza; Ayesha Javid; Zeeshan Ali; Muhammad Imran Khan; Faisal K. Algethami; Najla AlMasoud; Taghrid S. Alomar (Food Chemistry, 2025)

Development of tetraploids in tissue culture: modern techniques and biotechnological innovations - Sabeen Rehman Soomro; Salma Naimatullha Soomro; Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Muhammad Aasim; Heba I. Mohamed (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

A Global Perspective on the Biology, Impacts and Management Options of Leptochloa chinensis, a Noxious Weed of Direct-seeded Rice—A Review - Muhammad Ishfaq; Zarina Batool; Usman Zulfiqar; Muhammad Ahmad; Fasih Ullah Haider; Nasim Ahmed; Saddam Hussain; Shakeel Ahmed Anjum; Nadeem Akbar (Journal of Crop Health, 2025)

Ameliorative Effects of Silica on Growth, Antioxidant Response, and Metal Uptake in Chromium-Exposed Wheat - Khadija Ali; Muhammad Nadeem; Asia Khan; Rafia Mustafa; Muhammad Shabaan; Usman Zulfiqar; Sadam Hussain; Jawaher Alkahtani (Journal of Crop Health, 2025)

Synergistic anticancer effects of interleukin-21 combined with therapeutic peptides in multiple cancer cells - Muhammad Akram; Nao Akusa Fujimura; Saad Tahir; Rabia Abbas; Mohsin Ahmad Khan; Kausar Malik; Nadeem Ahmed (Biotechnology Letters, 2025)

Human Plasma-Derived Exosomes: A Promising Carrier System for the Delivery of Hydroxyurea to Combat Breast Cancer - Wajeeha Khalid; Afeefa Aslam; Nadeem Ahmed; Muhammad Sarfraz; Jawad Akbar Khan; Sabeeh Mohsin; Muhammad Shahid Riaz Rajoka; Imran Nazir; Muhammad Imran Amirzada (AAPS PharmSciTech, 2025)

Applicability of Start Codon Targeted (SCoT) markers for the assessment of genetic diversity in bread wheat germplasm - Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Amjad Ali; Waqas Liaqat; Mehmet Bedir; Nurettin Baran; Aleksandra Ilić; Muhammad Kashif Ilyas; Abdul Ghafoor; Hamide Dogan; Muhammad Aasim; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)
Research endeavors focused on examining genetic diversity play a pivotal role in advancing agricultural practices, as they furnish valuable insights for breeding programs and the preservation of germplasm. Wheat holds significant global importance as a cereal crop, serving as a primary source of sustenance for almost one-third of the global human population. In the current study, a total of 80 bread wheat genotypes were characterized using the start codon targeted (SCoT) marker system. A set of 14 polymorphic primers yielded a cumulative count of 399 bands with an average of 28.05 bands per primer. The range of diversity markers, such as polymorphism information content (0.26–0.59), effective numbers of alleles (1.27–1.59), Shannon’s information index (0.30–0.51), and gene diversity (0.18–0.34), provided evidence of elevated genetic differences within the examined germplasm. According to the findings of the molecular variance analysis, greater genetic variations are found within populations (92%). The model-based structural approach partitioned the 80 bread wheat genotypes into two distinct populations (Population A and B). The diversity indices based on the structures of the populations revealed that population A had greater diversity compared to population B. Both the principal coordinate analysis and the neighbor-joining analysis also differentiated the 80 different bread wheat genotypes based on their respective collection points. The present crop diversity offers great opportunities for enhancing crop quality and increasing tolerance to environmental challenges, both of which will lead to a reduction in the problem of food insecurity.

Systematic review on buparvaquone resistance associated with non-synonymous mutation in drug binding genes site of Theileria annulate - Muhammad Rashid; Muhammad Hassan Hayat; Naveed Zahra; Mian Sayed Khan; Suleman; Muhammad Nadeem; Tauseef ur Rehman; Muhammad Ehsan; Muhammad Irfan Malik; Muhammad Kashif Obaid; Amir Bakhsh; Mohamed Aziz Darghouth; et al. (Veterinary Parasitology, 2024)

Suppression of canary grass (Phalaris minor) with simultaneous use of rhizobacteria and sunflower allelopathy - Abubakar Dar; Umme Habiba; Muhammad Tauseef Jaffar; Maqshoof Ahmad; Azhar Hussain; Umar Farooq; Sajid Mehmood Nadeem; Muhammad Zahid Mumtaz; Usman Zulfiqar; Abd El-Zaher M.A. Mustafa; Mohamed S. Elshikh (Rhizosphere, 2024)

Assessing the combined impacts of microplastics and nickel oxide nanomaterials on soybean growth and nitrogen fixation potential - Imran Azeem; Quanlong Wang; Muhammad Adeel; Noman Shakoor; Muhammad Zain; Adnan Anwar khan; Yuanbo Li; Kamran Azeem; Muhammad Nadeem; Guikai Zhu; Rui Yukui (Journal of Hazardous Materials, 2024)

Nanoarchitectonics of molybdenum rich crown shaped polyoxometalates based ionic liquids reinforced on magnetic nanoparticles for the removal of microplastics and heavy metals from water - Hameed Ullah; Taghrid S. Alomar; Muhammad Tariq; Najla AlMasoud; Moazzam H. Bhatti; Muhammad Ajmal; Zahra Nazar; Muhammad Nadeem; Hafiz Muhammad Asif; Muhammad Sohail (Journal of Environmental Chemical Engineering, 2024)

Pre-emergence herbicide selection for successful cultivation of black seed (Nigella sativa L.), psyllium (Plantago ovata Forsk), and quinoa (Chenopodium quinoa Willd.) - Muhammad Zia Ul Haq; Saira Shafiq; Muhammad Zia Ul Mohsin; Majid Ali; Abdul Khaliq; Rana Nadeem Abbas; Muhammad Zafar Iqbal; Amar Matloob (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Role of exogenous silica fertilization and genotype selection in attenuating oxidative and osmotic stress in wheat (Triticum aestivum L.) under water deficit conditions - Muhammad Anwar ul Haq; Muhammad Nadeem; Munaza Naseem; Ghulam Hasan Abbasi; Muhammad Ali; Muhammad Ashar Ayub; Irfan Iftikhar; Muhammad Tayyab Mehmood; Muhammad Awais; Rizwan Ullah; Tasawar Ali (Plant and Soil, 2024)

Applicability of SCoT markers in unraveling genetic variation and population structure among sugar beet (Beta vulgaris L.) germplasm - Nazlı Aybar Yalinkiliç; Sema Başbağ; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Molecular Biology Reports, 2024)

Diagnostic and therapeutic value of EVs in lungs diseases and inflammation - Ali Afzal; Muhammad Babar Khawar; Ume Habiba; Hanan Afzal; Syeda Eisha Hamid; Mussarat Rafiq; Muddasir Hassan Abbasi; Nadeem Sheikh; Rimsha Abaidullah; Zoya Asif; Tahaa Saeed (Molecular Biology Reports, 2024)

Two new species of Lecaimmeria (lichenized Ascomycota, Lecideaceae) from Asia - Hafiza Simab Asghar; Muhammad Nadeem; Naqibullah Oryakhil; Iram Fayyaz; Abdul Rehman Niazi; Najam-ul-Sehar Afshan; Arooj Naseer; Abdul Nasir Khalid (Mycological Progress, 2024)

Salt Stress in Wheat: Effects, Tolerance Mechanisms, and Management - Muhammad Farooq; Noreen Zahra; Aman Ullah; Faisal Nadeem; Abdul Rehman; Riti Kapoor; Mawra S. Al-Hinani; Kadambot H.M. Siddique (Journal of Soil Science and Plant Nutrition, 2024)

Nanobiochar-Coating Regulates N and P Release from DAP Fertilizer in Soil and Improves Maize Crop Productivity - Ghulam Abbas Shah; Mughees Mustafa; Hani Z. Asfour; Khubra Shoukat; Ahsan Yasin; Nadeem Ali; Muhammad Bilal Khan Niazi; Gabrijel Ondrasek; Muhammad Imtiaz Rashid (Journal of Soil Science and Plant Nutrition, 2024)

Integrating MDT Tumor Board Shadowing into the Undergraduate Medical Curriculum: Perspective of Medical Students - Aasil Shayan Aziz; Masooma Shifa Rana; Salaar Ahmed; Muhammad Abdullah; Hafsa Khan Tareen; Ayesha Siddiq; Ahmed Nadeem Abbasi (Journal of Cancer Education, 2024)

Recombinant expression, downstream optimization, and therapeutic evaluation of recombinant human interleukin-37 for cancer therapy - Zaheer Abbas; Samia Afzal; Nao Akusa Fujimura; Muhammad Akram; Saad Tahir; Kausar Malik; Nadeem Ahmed (Biotechnology Letters, 2024)

Integrative metagenomic dissection of last-resort antibiotic resistance genes and mobile genetic elements in hospital wastewaters - Muhammad Shafiq; Xiaoling Guo; Meimei Wang; Hazrat Bilal; Li Xin; Yumeng Yuan; Fen Yao; Taha Majid Mahmood Sheikh; Muhammad Nadeem Khan; Xiaoyang Jiao (Science of The Total Environment, 2024)

Assessment of residues from common pesticides and associated risks in Pakistan - Muneer Abbas; Sohail Abbas; Niaz Hussain; Muhammad Tariq Javeed; Abdul Ghaffar; Muhammad Nadeem; Mudassar Khaliq; Sana Ullah; Zubeda Parveen; Khalid Ali Khan; Hamed A. Ghramh (Environmental Monitoring and Assessment, 2024)

Environmental Heavy Metal Exposure and Associated Cardiovascular Diseases in Light of the Triglyceride Glucose Index - Muhammad Bilal Sardar; Mohsin Raza; Ammara Fayyaz; Muhammad Asfandyar Nadir; Zain Ali Nadeem; Muhammad Babar (Cardiovascular Toxicology, 2024)

Oleuropein: Chemistry, extraction techniques and nutraceutical perspectives-An update - Anees Ahmed Khalil; Md. Mominur Rahman; Abdur Rauf; Md. Rezaul Islam; Sultana Juhara Manna; Ammar Ahmed Khan; Samee Ullah; Muhammad Nadeem Akhtar; Abdullah S. M. Aljohani; Waleed Al Abdulmonem; Jesus Simal-Gandara (Critical Reviews in Food Science and Nutrition, 2024)

Hydro-geochemistry and age-dependent health risk assessment of nitrate, nitrite, and fluoride in health facilities water: a multivariate analysis - Areej Nadeem; Behzad Murtaza; Muhammad Imran; Muhammad Shafique Khalid; Muhammad Shahid; Abdullah Ghardan Al-Sehemi; Yasar Nelliyot Kavil; Muhammad Amjad; Muhammad Wakeel (Environmental Science and Pollution Research, 2024)

Strategies and bibliometric analysis of legumes biofortification to address malnutrition - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Muhammad Faheem Jan; Faheem Shehzad Baloch; Celaleddin Barutçular; Muhammad Azhar Nadeem; Heba I. Mohamed (Planta, 2024)

Investigation of genetic diversity among autochthonous grape cultivars grown in Türkiye using molecular primers - Ahmet Sümbül; Ercan Yildiz; Ali Sabir; Muhammad Azhar Nadeem (Genetic Resources and Crop Evolution, 2024)
Grape is a type of fruit widely grown globally and in Türkiye thanks to its importance in human nutrition and diversity of usage areas. Türkiye has a long history of grape cultivation, and the genetic diversity of local grapes grown in some regions has still not been revealed. This study showed the genetic diversity between 60 local grape genotypes selected from north Central Anatolia and nine reference grape cultivars;10 inter simple sequence repeats (ISSR) and 7 inter-primer binding site (IPBS) retrotransposon primers were used. The mean values of genetic diversity indices in ISSR and IPBS retrotransposon primers were calculated as expected allelic frequency (p) 0.476/0.195, observed allelic frequency (q) 0.524/0.805, number of effective alleles (Ne) 1.326/1.378, Shannon’s information index (I) 0.308/0.367, expected heterozygosity (He) 0.199/0.232 and unbiased expected heterozygosity (uHe) 0.201/0.234, respectively. Unweighted pair group method with arithmetic mean (UPGMA) and model-based STRUCTURE analysis divided the studied germplasm into two groups. However, local genotypes were not grouped per the regions where they grew. As a result of the analysis of molecular variance (AMOVA) analysis, the inter-population variation was determined to be 11%, and the intra-population variation was determined to be 89%. The mean genetic differentiation value (Fst) between populations was 0.303. The results showed that ISSR and IPBS retrotransposon primers effectively explained the genetic diversity.

Investigation of therapeutic potential of the Il24-p20 fusion protein against breast cancer: an in-silico approach - Shahnila Qureshi; Nadeem Ahmed; Hafiz Muhammad Rehman; Muhammad Imran Amirzada; Fiza Saleem; Kainat Waheed; Afeefa Chaudhry; Iram Kafait; Muhammad Akram; Hamid Bashir (In Silico Pharmacology, 2024)

Health risk assessment of bread wheat grown under cadmium and nickel stress and impact of silicic acid application on its growth, physiology, and metal uptake - Alina Shafiq; Muhammad Emmad Munawar; Muhammad Nadeem; Asia Khan; Ghulam Hasan Abbasi; Muhammad Anwar ul Haq; Muhammad Ashar Ayub; Irfan Iftikhar; Muhammad Awais (Environmental Science and Pollution Research, 2024)

Photocatalytically active layered double hydroxide-PVDF composite membranes for effective remediation of dyes contaminated water - Mukarram Zubair; Muhammad Yasir; Michal Machovsky; Nadeem Baig; Mohammad Saood Manzar; Jehad Abdulfatah Sadeq Odeh; Mohamed K. Hassan; Alaa Hawari; Jehad Odeh; Emre Cevik; Maryam Al-Ejji (Chemosphere, 2024)

Incorporating Halal Into Healthy and Equitable Dietary Patterns to Address Food and Nutrition Security Among K-12 and University Students: A Perspective - Amelia Keleher; Meira Neggaz; Christine M. Cliff; YaQutullah Ibraheem Muhammad; Anne Mathews; Habeeb Quadri; Ridwan Abdul Rashid; Nadeem Zafar; Asma Ahad (Journal of Nutrition Education and Behavior, 2024)

Frontiers in bacterial-based green synthesized nanoparticles (NPs): A sustainable strategy for combating infectious plant pathogens - Amjad Ali; Muhammad Aasim; Kübra Çelik; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Biocatalysis and Agricultural Biotechnology, 2024)

Alleviating Drought Stress in Strawberry Plants: Unraveling the Role of Paclobutrazol as a Growth Regulator and Reducer of Oxidative Stress Induced by Reactive Oxygen and Carbonyl Species - Khansa Saleem; Muhammad Ahsan Asghar; Ali Raza; Kaiwen Pan; Abd Ullah; Hafiz Hassan Javed; Mahmoud F. Seleiman; Shakeel Imran; Sajid Mehmood Nadeem; Khurram Shehzad Khan; Junbo Du; Fei Xu; et al. (Journal of Plant Growth Regulation, 2024)

Integrative approach to the biochemical, and toxicological fingerprinting of Polygonum glabrum.: A computational and experimental synergy for a medicinal food plant - Sumera Hanif; Muhammad Faisal Nadeem; Haji M. Shoaib Khan; Muhammad Naeem; Anjum Khursheed; Abdulwahab Alamri; Mhdia Elhadi Osman; Adel Alghamdi; Nasrin E. Khalifa; Marcello Locatelli; Syafiq Asnawi Zainal Abidin (Food Bioscience, 2024)

Quantitative and qualitative approach for accessing and predicting food safety using various web-based tools - Hafiz Muhammad Rizwan Abid; Nimrah Khan; Athar Hussain; Zainab Bintay Anis; Muhammad Nadeem; Nauman Khalid (Food Control, 2024)

Retraction Note: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Stripe rust resistance gene Yr15 in Turkish and Kazakhstan wheat germplasms and the potential of Turkish wild emmer for stripe rust breeding - Faheem Shehzad Baloch; Amjad Ali; Daniyar Tajibayev; Muhammad Azhar Nadeem; Fatih Ölmez; Hüsnü Aktaş; Ahmad Alsaleh; Gönül Cömertpay; Mustafa Imren; Zemran Mustafa; Abdelfattah A. Dababat; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2024)

Design and optimization of off-grid solar PV and biomass-based hybrid renewable energy system (HRES) for electrification of a rural community in Tharparkar, Pakistan - Talha Bin Nadeem; Ahsan Ahmed; Muhammad Saad; Asad A. Naqvi (Environment, Development and Sustainability, 2024)

Impact of spray drying operating conditions on yield, secondary metabolites, antioxidant potential and storage quality of grape (Vitis vinifera L.) pomace powder - Aurbab Shoukat; Muhammad Imran; Muhammad Kamran Khan; Muhammad Haseeb Ahmad; Rabia Shabir Ahmad; Mohamed Fawzy Ramadan; Muhammad Nadeem; Adeela Yasmin; Muhammad Abdul Rahim; Muhammad Imran Khan (South African Journal of Botany, 2024)

RETRACTED: Boosted charge separation via Ce2S3 over dual Z-scheme ZnO–Ce2S3–MnO2 core double-shell nanocomposite for the degradation of diverse dye pollutants - Tauseef Munawar; Taghrid S. Alomar; Chang-Feng Yan; Saman Fatima; Faisal Mukhtar; Muhammad Shahid Nadeem; Najla AlMasoud; Shoukat Alim Khan; Muammer Koc; Yahya Zakaria; Faisal Iqbal (Environmental Research, 2024)

Assessment of molecular and metabolic traits of a newly isolated Spirulina platensis BERC15 in a low-cost cultivation alternative for its use as functional food - Muhammad Aamer Mehmood; Mahwish Amin; Muhammad Adnan Ul Haq; Ayesha Shahid; Sana Malik; Amna Jabbar Siddiqui; Ning Wang; Hui Zhu; Azhar Rasul; Ahmed Hassan Chaudhry; Khalid Nadeem; Raj Boopathy; et al. (Bioresource Technology Reports, 2024)

Review of the potential pharmacological role of erucic acid: a monounsaturated omega-9 fatty acid - Imran Kazmi; Muhammad Afzal; Fahad A. Al-Abbasi; Shareefa A. AlGhamdi; Amira M. Alghamdi; Sami I. Alzarea; Waleed Hassan Almalki; Abeer S. AlGhamdi; Khadijah B. Alkinani; Nadeem Sayyed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Soil Organic Carbon and Nitrogen Mineralization Potential of Manures Regulated by Soil Microbial Activities in Contrasting Soil Textures - Waqar Ahmed; Muhammad Nadeem Ashraf; Muhammad Sanaullah; Muhammad Aamir Maqsood; Muhammad Ahmed Waqas; Shafeeq Ur Rahman; Saddam Hussain; Hammad Raza Ahmad; Adnan Mustafa; Xu Minggang (Journal of Soil Science and Plant Nutrition, 2024)

Zinc Provisioned Enhancement of Manganese Use Efficiency Results in Differential Biomass and Grain Production in Two Rice Cultivars Grown in Clay Loam Soil - Faisal Nadeem; Rashid Mahmood; Muhammad Anwar-ul-Haq; Muhammad Sabir; Saifullah; Qingxu Ma; Chongwei Jin; Tayyaba Samreen; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2024)

Elucidating the genetic diversity and population structure of international cotton germplasm using inter-primer binding site (iPBS) retrotransposon marker system - Binnur Yeşil Bayrıl; Allah Bakhsh; Muhammad Azhar Nadeem; Ufuk Demirel (Genetic Resources and Crop Evolution, 2024)

Cu-TiO2-Aluminosilicate Nanocomposite as Highly Efficient Photocatalyst for Sustainable Removal of Cefixime Antibiotic: Synthesis, Optimization, and Toxicity Evaluation - Muhammad Umar Farooq; Qurat-Ul-Ain; Muhammad Irfan Jalees; Mahnoor Abid; Mirza Nadeem Ahmad; Maira Kaleem; Asma Tufail Shah; Juan Joon Ching (Environmental Processes, 2024)

Recent advancements in modifications of metal–organic frameworks-based materials for enhanced water purification and contaminant detection - Hai Bang Truong; Van Nhieu Le; Muhammad Nadeem Zafar; Iqra Rabani; Ha Huu Do; Xuan Cuong Nguyen; Vu Khac Hoang Bui; Jin Hur (Chemosphere, 2024)

Cryptic footprint of thallium in soil-plant systems; A review - Noman Shakoor; Samama Tariq; Muhammad Adeel; Imran Azeem; Muhammad Nadeem; Muhammad Zain; Yuanbo Li; Wang Quanlong; Rabia Aslam; Yukui Rui (Chemosphere, 2024)

Machine learning assisted prediction of solar to liquid fuel production: a case study - Muhammad Wakil Shahzad; Viet Hung Nguyen; Ben Bin Xu; Rasikh Tariq; Muhammad Imran; Waqar Muhammad Ashraf; Kim Choon Ng; Muhammad Ahmad Jamil; Amna Ijaz; Nadeem Ahmed Sheikh (Process Safety and Environmental Protection, 2024)

Investigating the quantum size effects of multi-walled carbon nanotubes (MWCNTs) in photocatalytic fermentative biohydrogen production - Hina Ramzan; Faiqa Nadeem; Muhammad Usman; Muhammad Shahzaib; Muneeb Ur Rahman; Fuhua Shen; Zhiping Zhang; Reeta Rani Singhania; Farzana Jabeen; Waheed Afzal; Nadeem Tahir (Journal of Cleaner Production, 2024)

Artificial intelligence models for validating and predicting the impact of chemical priming of hydrogen peroxide (H2O2) and light emitting diodes on in vitro grown industrial hemp (Cannabis sativa L.) - Muhammad Aasim; Buşra Yıldırım; Ahmet Say; Seyid Amjad Ali; Selim Aytaç; Muhammad Azhar Nadeem (Plant Molecular Biology, 2024)

Biochar: Black Gold for Sustainable Agriculture and Fortification Against Plant Pathogens—A Review - Usman Arshad; Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Ali; Muhammad Nadeem Shah; Muhammad Jabran; Muhammad Amjad Ali (Journal of Crop Health, 2024)

Dynamic linkages between carbon emission, energy utilization, financial growth and economic growth: evidence from SAARC - Huizhu Tan; Nazmia Elahi; Aftab Hussain Tabasam; Hira Abdul Rawoof; Rabia Saghir; Muhammad Nadeem Khan (Environment, Development and Sustainability, 2024)

Linking energy-based circularity with environment in high-income economies - Muhammad Usman; Syed Asif Ali Naqvi; Sofia Anwar; Abdul Majeed Nadeem (Environmental Science and Pollution Research, 2024)

Recent advances in applications of marine hydrocolloids for improving bread quality - Anum Ishaq; Muhammad Nadeem; Rafiq Ahmad; Zahoor Ahmed; Nauman Khalid (Food Hydrocolloids, 2024)

Vegetable Plant Canopy Inhibits Soil Urease Activity and Reduces NH3 Losses Under p-Phenylenediamine (PPD)-Coated Urea Application - Sarah Shakeel; Rashid Mahmood; Ammara Fatima; Faisal Nadeem; Sajid Ali; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2024)

Long-term straw returning improved soil nitrogen sequestration by accelerating the accumulation of amino acid nitrogen - Lei Xu; Hong Chen; Yan Zhou; Jianwei Zhang; Muhammad Yousaf Nadeem; Congrong Miao; Jiahui You; Weiwei Li; Yu Jiang; Yanfeng Ding; Ganghua Li (Agriculture, Ecosystems & Environment, 2024)

Remediation of organic pollutant from the aqueous environment using in-house fabricated polyaniline-based hybrid composite (PANI-MnPBA/NiCoMnS) materials - Naseem Ahmad Khan; Muhammad Imran; Muhammad Nadeem Akhtar; Shabbir Hussain; Muhammad Azhar Khan; Ashwag Shami; Hafiz Iqbal (Chemosphere, 2024)

Role of biogas slurry to reclaim soil properties providing an eco-friendly approach for crop productivity - Asif Mukhtiar; Athar Mahmood; Muhammad Anjum Zia; Muaz Ameen; Renji Dong; Yang Shoujun; Muhammad Mansoor Javaid; Bilal Ahmad Khan; Muhammad Ather Nadeem (Bioresource Technology Reports, 2024)

Foliar Glutamine Application Improves Grain Yield and Nutritional Quality of Field-Grown Maize (Zea mays L.) Hybrid ZD958 - Md Monirul Islam; Mahmood Ul Hassan; Muhammad Ishfaq; Farhana Alam Ripa; Faisal Nadeem; Zeeshan Ahmad; Jiuliang Xu; Peng Ning; Xuexian Li (Journal of Plant Growth Regulation, 2024)

Scalable synthesis of MOF-derived Nd2O3@C and V2O5@C nanohybrid: Efficient electrocatalyst for OER in alkaline medium - Tauseef Munawar; Ambreen Bashir; Muhammad Shahid Nadeem; Faisal Mukhtar; Sumaira Manzoor; Muhammad Naeem Ashiq; Shoukat Alim Khan; Muammer Koc; Faisal Iqbal (Fuel, 2024)

Magnetic solid phase extraction of aminoglycosides residue in chicken egg samples using Fe3O4-GO-Agarose-Chitosan composite - Muhammad Sajjad; Rasmiah Almufarij; Zeeshan Ali; Muhammad Sajid; Nadeem Raza; Suryyia Manzoor; Muhammad Hayat; Ehab A. Abdelrahman (Food Chemistry, 2024)

Emerging role of lipophagy in liver disorders - Bismillah Nazeer; Muhammad Babar Khawar; Muhammad Usman Khalid; Syeda Eisha Hamid; Mussarat Rafiq; Muddasir Hassan Abbasi; Nadeem Sheikh; Ahmad Ali; Hooriya Fatima; Sadia Ahmad (Molecular and Cellular Biochemistry, 2024)

Genome-wide association studies revealed DArTseq loci associated with agronomic traits in Turkish faba bean germplasm - Tolga Karaköy; Faruk Toklu; Eylem Tuğay Karagöl; Damla Uncuer; Yeter Çilesiz; Amjad Ali; Muhammad Azhar Nadeem; Hakan Özkan (Genetic Resources and Crop Evolution, 2024)

Geo-statistical analysis of climatic variability and trend detection in the Hindu Kush region, North Pakistan - Muhammad Dawood; Atta-ur Rahman; Ghani Rahman; Basit Nadeem; Muhammad Miandad (Environmental Monitoring and Assessment, 2024)

Coal fly ash supported Ag@Bi2WO6: A novel heterogeneous nanocomposite for effective sunlight driven photocatalytic degradation of dye - Muhammad Zubair Saleem; Nimra Nadeem; Muhammad Shahbaz; Nabil Al-Zaqri; Shahid Rasul; Saima Noreen; Muhammad Zahid; Imran shahid (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Alteration of microbial carbon and nitrogen metabolism within the soil metagenome with grazing intensity at semiarid steppe - Zhen Wang; Kai Tang; Paul C. Struik; Muhammad Nadeem Ashraf; Tongrui Zhang; Yanning Zhao; Riliga Wu; Ke Jin; Yuanheng Li (Journal of Environmental Management, 2023)

Corrigendum to “Automated anomalous behaviour detection in soil radon gas prior to earthquakes using computational intelligence techniques” [J. Environ. Radioact. 203 (2019) 48-54] - Aleem Dad Khan Tareen; Asim Khawaja; Kimberlee Jane Kearfott; Muhammad Rafique; Malik Sajjad Ahmed Nadeem; Talat Iqbal; Saeed Ur Rahman (Journal of Environmental Radioactivity, 2023)

Spatio-temporal patterns of human-carnivore conflict and mitigation in Pakistan - Muhammad Danish; Tariq Mahmood; Faraz Akrim; Muhammad Sajid Nadeem; Shumaila Noreen; Nadeem Munawar; Muhammad Shakil; Muhammad Arshad (Journal for Nature Conservation, 2023)

Impact of different proportions of sweet potato (Ipomoea batatas L.) flour on physical, chemical and sensory parameters of straight grade flour-based cake rusk - Hafiza Saher Rafique; Ashiq Hussain; Muhammad Nadeem; Abdul Rehman; Tahira Siddique; Ayesha Najam; Haseeb Haroon; Muhammad Rehan Arif; Shazia Yaqub; Haya Fatima; Salah Laaraj (Food and Humanity, 2023)

Controlled-release potassium blended fertilizer mitigates greenhouse gas emissions in paddy fields - Sajjad Ahmad; Shen Gao; Quanxin Li; Muhammad Yousaf Nadeem; Weike Tao; Fei Yang; Yanfeng Ding; Zhenghui Liu; Ganghua Li (Nutrient Cycling in Agroecosystems, 2023)

Fabrication and Evaluation of Differential Release Bilayer Tablets of Clarithromycin and Levofloxacin by 3D Printing - Qazi Amir Ijaz; Sumera Latif; Sumaira Irum Khan; Memoona Rashid; Hafsa Afzal; Nasrullah Jan; Zeeshan Javaid; Muhammad Sarfraz; Amjad Hussain; Muhammad Sohail Arshad; Nadeem Irfan Bukhari; Nasir Abbas (Journal of Pharmaceutical Innovation, 2023)

Genetic characterization of coarse and basmati rice (Oryza sativa L.) through microsatellite markers and morpho-agronomic traits - Tahira Luqman; Zia-ul Qamar; Aqsa Tabasum; Wael. H. El-Kallawy; Talha Nazir; Safira Attacha; Sajid Fiaz; Muhammad Azhar Nadeem; Amjad Hameed; Zahra Maryum; Itoh Kimiko; Kotb Attia (Genetic Resources and Crop Evolution, 2023)

Risk assessment of trace element accumulation in soil and Brassica oleracea after wastewater irrigation - Ali Haider Shah; Muhammad Shahid; Maria Tahir; Natasha Natasha; Irshad Bibi; Tasveer Zahra Tariq; Sana Khalid; Muhammad Nadeem; Ghulam Abbas; Muhammad Farhan Saeed; Sabah Ansar; Camille Dumat (Environmental Geochemistry and Health, 2023)

Synergistic effect of microwave heating and thermosonication on the physicochemical and nutritional quality of muskmelon and sugarcane juice blend - Pinky Fatima; Muhammad Nadeem; Ashiq Hussain; Tusneem Kausar; Abdul Rehman; Tahira Siddique; Khurram Kabir; Saima Noreen; Rizwan Nisar; Haya Fatima; Sameh A. Korma; Jesus Simal-Gandara (Food Chemistry, 2023)

Thin-film nanocomposite membranes for efficient removal of emerging pharmaceutical organic contaminants from water - Asif Matin; Nadeem Baig; Deepak Anand; Irshad Ahmad; Muhammad Sajid; Muhammad Saqib Nawaz (Environmental Research, 2023)

Drug–ionic surfactant interactions: density, sound speed, spectroscopic, and electrochemical studies - Muhammad Sohail; Hafiz Muhammad Abd Ur Rahman; Muhammad Nadeem Asghar (European Biophysics Journal, 2023)

Evaluation of possible attenuative role of chrysoeriol against polyethylene microplastics instigated testicular damage: A biochemical, spermatogenic and histological study - Muhammad Umar Ijaz; Faria Saher; Nemra Aslam; Ali Hamza; Haseeb Anwar; Saad Alkahtani; Hammad Ahmad Khan; Mian Nadeem Riaz (Food and Chemical Toxicology, 2023)

Depolymerization of lignin: Recent progress towards value-added chemicals and biohydrogen production - Hina Ramzan; Muhammad Usman; Faiqa Nadeem; Muhammad Shahzaib; Muneeb Ur Rahman; Reeta Rani Singhania; Farzana Jabeen; Anil Kumar Patel; Chunyao Qing; Shengyong Liu; Grzegorz Piechota; Nadeem Tahir (Bioresource Technology, 2023)

Triggering photo fermentative biohydrogen production through NiFe2O4 photo nanocatalysts with various excitation sources - Shengyong Liu; Fuhua Shen; Faiqa Nadeem; Muneeb Ur Rahman; Muhammad Usman; Hina Ramzan; Muhammad Shahzaib; Reeta Rani Singhania; Wang Yi; Chunyao Qing; Nadeem Tahir (Bioresource Technology, 2023)

Exploring the role of HaTIPs genes in enhancing drought tolerance in sunflower - Tania Safdar; Muhammad Hammad Nadeem Tahir; Zulfiqar Ali; Muhammad Habib ur Rahman (Molecular Biology Reports, 2023)

Probiotic characterization of Bacillus species strains isolated from an artisanal fermented milk product Dahi - Muhammad Nadeem Khan; Saeeda Bashir; Muhammad Imran (Folia Microbiologica, 2023)

Assessment of radiological indices and physiochemical characterization of sediments in Chashma Lake, Pakistan - Mustafa Khan; Muhammad Zaman Chaudhary; Ehsan Ullah Khan; Jawaria Abid; Tabassum Nasir; Nadeem Yaqoob (Environmental Monitoring and Assessment, 2023)

Mucoadhesive, Fluconazole-Loaded Nanogels Complexed with Sulfhydryl-β-cyclodextrin for Oral Thrush Treatment - Farwa Muskan Khalid; Muhammad Ijaz; Arshad Mahmood; Muhammad Khurram Waqas; Talib Hussain; Mulazim Hussain Asim; Nadeem Ahmad; Shumaila Arshad; Masood Ur Rehman; Imran Nazir (AAPS PharmSciTech, 2023)

Alleviation of arsenic toxicity-induced oxidative stress in lemon grass by methyl jasmonate - Khansa Saleem; Muhammad Ahsan Asghar; Hafiz Hassan Javed; Ali Raza; Mahmoud F. Seleiman; Abd Ullah; Altafur Rahman; Sufyan Iqbal; Aamir Hanif; Shakeel Imran; Sajid Mahmood Nadeem; Junbo Du; et al. (South African Journal of Botany, 2023)

OsBBX19-OsBTB97/OsBBX11 module regulates spikelet development and yield production in rice - Abdullah Shalmani; Uzair Ullah; Li Tai; Ran Zhang; Xiu-Qing Jing; Izhar Muhammad; Nadeem Bhanbhro; Wen-Ting Liu; Wen-Qiang Li; Kun-Ming Chen (Plant Science, 2023)

Transforming Bombax ceiba L. sawdust waste into a valuable growth substrate: An example with sugarcane - Muhammad Yasin; Muhammad Usman Zia; Athar Mahmood; Muhammad Mansoor Javaid; Muhammad Ather Nadeem; Christian Andreasen (Bioresource Technology Reports, 2023)

Effect of heterologous platelet-rich plasma on liver and modulation of glucose metabolism and Wnt signalling pathways in diabetic mice - Amin Arif; Adil Farooq; Muddasir Hassan Abbasi; Muhammad Babar Khawar; Tasleem Akhtar; Humaira Allay Ali; Mehreen Anjum; Rabia Mehmood; Tayyaba Saleem; Nadeem Sheikh (Molecular Biology Reports, 2023)

Improving Nitrogen Acquisition and Utilization Through Root Architecture Remodelling: Insight from Legumes - Muhammad Nadeem; Muhammad Yahya; Jingyang Tong; Liaqut Shah; Sana Ullah Khan; Ahmad Ali; Alam Sher; Najeeb Ullah; Abdul Waheed (Journal of Plant Growth Regulation, 2023)
In crop species, nutrient deficiency severely damages plant growth and developmental processes, leading to end-yield penalties. Root architecture remodelling is considered a key factor underpinning nutrient-poor soil environments. Adequate nitrogen (N) supply can play a significant role in sustaining crop productivity on nutrient-deficient soils. However, excessive application of nitrogenous fertilizer may pollute the soil and increase the production cost for the growers. To tackle this problem, crop breeders have made tremendous efforts to improve the N-use efficiency of agricultural crops. This article summarizes the recent progress in identifying QTLs/genes, regulatory pathways, and hormonal crosstalk involved in the growth and development of legumes roots system. Moreover, we have described the progress in microbe–root symbiosis via QTLs/genes regulations, which results in improved N acquisition. Understanding the molecular mechanisms that regulate the root architecture in response to N availability may help to strengthen the root system of legumes and promote environmental friendly and sustainable agriculture.

Advancing sustainable growth and energy transition in the United States through the lens of green energy innovations, natural resources and environmental policy - Sami Ullah; Rundong Luo; Muhammad Nadeem; Javier Cifuentes-Faura (Resources Policy, 2023)

Nanobiochar reduces ammonia emission, increases nutrient mineralization from vermicompost, and improves maize productivity - Muhammad Imtiaz Rashid; Ghulam Abbas Shah; Zahid Iqbal; Khurram Shahzad; Nadeem Ali; Mohammad Rehan; Nabil Abdulhafiz A. Alhakamy; Jiří Jaromír Klemeš (Journal of Cleaner Production, 2023)

Insight into crustacean cathepsins: Structure-evolutionary relationships and functional roles in physiological processes - Isma Gul; Muhammad Nadeem Abbas; Saima Kausar; Jili Luo; Xinyue Gao; Yuhang Mu; Wenhui Fan; Honghuan Cui (Fish & Shellfish Immunology, 2023)

Advances in the catalyzed photo-fermentative biohydrogen production through photo nanocatalysts with the potential of selectivity, and customization - Faiqa Nadeem; Huan Zhang; Nadeem Tahir; Zhiping Zhang; Reeta Rani Singhania; Muhammad Shahzaib; Hina Ramzan; Muhammad Usman; Muneeb Ur Rahman; Quanguo Zhang (Bioresource Technology, 2023)

Natural disasters, resilience-building, and risk: achieving sustainable cities and human settlements - Muhammad Tariq Iqbal Khan; Sofia Anwar; Samuel Asumadu Sarkodie; Muhammad Rizwan Yaseen; Abdul Majeed Nadeem; Qamar Ali (Natural Hazards, 2023)

iPBS-retrotransposons variations: DNA fingerprinting and the evaluation of genetic diversity and population structure in international cowpea germplasm - Faheem Shehzad Baloch; Muhammad Tanveer Altaf; Mehmet Bedir; Muhammad Azhar Nadeem; Muhammed Tatar; Tolga Karaköy; Muhammad Aasim (Genetic Resources and Crop Evolution, 2023)

Enhanced soluble expression of active recombinant human interleukin-29 using champion pET SUMO system - Ayesha Munir; Nadeem Ahmed; Muhammad Akram; Nao Akusa Fujimura; Saad Tahir; Kausar Malik (Biotechnology Letters, 2023)

Seismic risk assessment and hotspots prioritization: a developing country perspective - Rehan Asad; Muhammad Qaiser Saleem; Muhammad Salman Habib; Nadeem Ahmad Mufti; Shaker Mahmood Mayo (Natural Hazards, 2023)

Carbon neutrality along the way to participate in global value chains: the threshold effect of information globalization of BRICS countries - Tingting Liu; Muhammad Nadeem; Zilong Wang; Pomi Shahbaz (Environmental Science and Pollution Research, 2023)

RETRACTED: Source, occurrence, distribution, fate, and implications of microplastic pollutants in freshwater on environment: A critical review and way forward - Tonni Agustiono Kurniawan; Ahtisham Haider; Hafiz Muhammad Ahmad; Ayesha Mohyuddin; Hafiz Muhammad Umer Aslam; Sohail Nadeem; Mohsin Javed; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Kit Wayne Chew (Chemosphere, 2023)

A step towards achieving SDG 2030 agenda: Analyzing the predictive power of information globalization amidst technological innovation-environmental stewardship nexus in the greenest economies - Muhammad Ramzan; Sami Ullah; Syed Ali Raza; Muhammad Nadeem (Journal of Environmental Management, 2023)

Artificial neural network and decision tree facilitated prediction and validation of cytokinin-auxin induced in vitro organogenesis of sorghum (Sorghum bicolor L.) - Muhammad Aasim; Seyid Amjad Ali; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shahzad Baloch (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Exploring the genetic diversity and population structure of upland cotton germplasm by iPBS-retrotransposons markers - Nurettin Baran; Flavien Shimira; Muhammad Azhar nadeem; Muhammad Tanveer altaf; Mehtap andirman; Faheem Shehzad Baloch; Mefhar Gültekin Temiz (Molecular Biology Reports, 2023)

Composted Melia azedarach L. (Chinaberry tree) Sawdust Mixtures Regulate the Sprouting and Growth of Single Bud Node Seedlings of Sugarcane - Mehwish Sultan Ahmed; Muhammad Yasin; Muhammad Usman Zia; Muhammad Ather Nadeem; Sher Muhammad; Athar Mahmood (Journal of Soil Science and Plant Nutrition, 2023)

Elucidating the genetic variations among Turkish grape varieties using morphological and molecular markers - Ahmet Sümbül; Ercan Yildiz; Muhammad Azhar Nadeem (Genetic Resources and Crop Evolution, 2023)

Natural resources, fiscal decentralization, and environmental quality in China: an empirical analysis from QARDL approach - Mei Zhang; Muhammad Hafeez; Chaudhry Muhammad Nadeem Faisal; Muhammad Shahzad Iqbal (Environmental Science and Pollution Research, 2023)

Long-term manure application increased soil organic carbon and nitrogen mineralization through accumulation of unprotected and physically protected carbon fractions - Muhammad Nadeem ASHRAF; Cheng HU; Xiangru XU; Tariq AZIZ; Lei WU; Muhammad Ahmed WAQAS; Muhammad FAROOQ; Xu HU; Wenju ZHANG; Minggang XU (Pedosphere, 2023)

Influence of ionic cerium and cerium oxide nanoparticles on Zea mays seedlings grown with and without cadmium - Muhammad Ashar Ayub; Muhammad Zia ur Rehman; Hamaad Raza Ahmad; John-Paul Fox; Preston Clubb; Alan L. Wright; Muhammad Anwar-ul-Haq; Muhammad Nadeem; Cyren M. Rico; Lorenzo Rossi (Environmental Pollution, 2023)

RETRACTED ARTICLE: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Co-pyrolysis of sewage sludge and biomass for stabilizing heavy metals and reducing biochar toxicity: A review - Badr A. Mohamed; Roger Ruan; Muhammad Bilal; Nadeem A. Khan; Mukesh Kumar Awasthi; Mariam A. Amer; Lijian Leng; Mohamed A. Hamouda; Dai‑Viet Nguyen Vo; Jian Li (Environmental Chemistry Letters, 2023)
The huge amounts of sewage sludge produced by municipal wastewater treatment plants induce major environmental and economical issues, calling for advanced disposal methods. Traditional methods for sewage sludge disposal increase greenhouse gas emissions and pollution. Moreover, biochar created from sewage sludge often cannot be used directly in soil applications due to elevated levels of heavy metals and other toxic compounds, which alter soil biota and earthworms. This has limited the application of sewage sludge-derived biochar as a fertilizer. Here, we review biomass and sewage sludge co-pyrolysis with a focus on the stabilization of heavy metals and toxicity reduction of the sludge-derived biochar. We observed that co-pyrolyzing sewage sludge with biomass materials reduced heavy metal concentrations and decreased the environmental risk of sludge-derived biochar by up to 93%. Biochar produced from sewage sludge and biomass co-pyrolysis could enhance the reproduction stimulation of soil biota by 20‒98%. Heavy metals immobilization and transformation are controlled by the co-feed material mixing ratio, pyrolysis temperature, and pyrolysis atmosphere.

Functional characterization of transcriptional activator gene SIARRI in tomato reveals its role in fruit growth and ripening - Muhammad Fahad; Muhammad Tanveer Altaf; Amna Jamil; Abdul Basit; Muhammad Mudassir Aslam; Waqas Liaqat; Muhammad Nadeem Shah; Izhar Ullah; Heba I. Mohamed (Transgenic Research, 2023)

Bioplastics from waste biomass of marine and poultry industries - Amna Arif; Farrukh Azeem; Ijaz Rasul; Muhammad Hussnain Siddique; Muhammad Zubair; Faizan Muneer; Warda Zaheer; Habibullah Nadeem (Journal of Biosciences, 2023)

Metal organic frameworks as promising sensing tools for electrochemical detection of persistent heavy metal ions from water matrices: A concise review - Syed Salman Shafqat; Muhammad Rizwan; Maria Batool; Syed Rizwan Shafqat; Ghulam Mustafa; Tahir Rasheed; Muhammad Nadeem Zafar (Chemosphere, 2023)

Detection and quantification of aflatoxins in spices stored in different food packaging materials - Muhammad Abrar; Samreen Ahsan; Muhmmad Nadeem; Atif Liaqat; Muhmmad Farhan Jahangir Chughtai; Muhammad Adil Farooq; Tariq Mehmood; Adnan Khaliq; Ayesha Siddiqa (Journal of Stored Products Research, 2023)

Enhanced charge separation in dual Z-scheme Au decorated LaFeO3-g-C3N4-BiFeO3 system for efficient H2 production - Nayab Arif; Yunfei Ma; Muhammad Ahsan Iqbal; Muhammad Nadeem Zafar; Huawei Liang; Qitao Zhang; Yu-Jia Zeng (Fuel, 2023)

A comprehensive review on phytochemistry, bioactivity and medicinal value of bioactive compounds of pomegranate (Punica granatum) - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Lufeng Wang; Shafeeqa Irfan; Muhammad Naeem Safdar; Mian Anjum Murtaza; Muhammad Nadeem; Shahid Mahmood; Ghulam Mueen-ud-Din; Hafiz Rehan Nadeem (Advances in Traditional Medicine, 2023)

Photocatalytic degradation of industrial dye using hybrid filler impregnated poly-sulfone membrane and optimizing the catalytic performance using Box-Behnken design - Sadaf Ul Hassan; Sidra Shafique; Bushra Anees Palvasha; Muhammad Haris Saeed; Syed Ali Raza Naqvi; Sohail Nadeem; Syed Irfan; Toheed Akhter; Asim Laeeq Khan; Muhammad Shahid Nazir; Murid Hussain; Young-Kwon Park (Chemosphere, 2023)

A comparative study based on performance and techno-economic analysis of different strategies for PV-Electrolyzer (green) hydrogen fueling incinerator system - Osama Majeed Butt; Muhammad Shakeel Ahmad; Teong Kai Lun; Hang Seng Che; H. Fayaz; Nasrudin Abd Rahim; Krzysztof K.K. Koziol; Neyara Radwan; Mohammad Amir Khan; Nadeem A Khan; Lakhveer Singh (Waste Management, 2023)

Dual functionalized Ag plasmonic sensor for colorimetric detection of Cr(III)/Hg(II)-carboxyl complexes: Mechanism and its sensing based on the interference of organic ligand - L. Sruthi; Mohammad Asad; Muhammad Nadeem Arshad; Abdullah M. Asiri; S. Sudheer Khan (Journal of Environmental Chemical Engineering, 2023)

Experimental design by response surface methodology for efficient cefixime uptake from hospital effluents using anion exchange membrane - Muhammad Ali Khan; Nadeem Raza; Suryyia Manzoor; Ramsha Shuja; Hina Raza; Muhammad Imran Khan; Mudassar Azam; Abdallah Shanableh (Chemosphere, 2023)

Advanced experimental techniques for the sensitive detection of a toxic bisphenol A using UiO-66-NDC/GO-based electrochemical sensor - T.S. Sunil Kumar Naik; Simranjeet Singh; Pavithra N; Radhika Varshney; Basavaraju Uppara; Joginder Singh; Nadeem A. Khan; Lakhveer Singh; Muhammad Zulqarnain Arshad; Praveen C. Ramamurthy (Chemosphere, 2023)

Optimization of carboxylated graphene oxide (C-GO) content in polymer matrix: Synthesis, characterization, and application study - Zulfiqar Ahmad Rehan; Muhammad Zahid; Sidra Kanwal; Nimra Nadeem; Asif Hafeez; Asif Jamil; Zakariya Zubair (Chemosphere, 2023)

Profiling of phthalates, brominated, and organophosphate flame retardants in COVID-19 lockdown house dust; implication on the human health - Nadeem Ali; Muhammad Imtiaz Rashid; Nabil A. Alhakamy; Sultan Hassan Alamri; Syed Ali Musstjab Akber Shah Eqani (Science of The Total Environment, 2023)

Zinc oxide nanoparticles mediated biostimulant impact on cadmium detoxification and in silico analysis of zinc oxide-cadmium networks in Zea mays L. regulome - Yashfa Tanveer; Saman Jahangir; Zafar Abbas Shah; Humaira Yasmin; Asia Nosheen; Muhammad Nadeem Hassan; Noshin Illyas; Andrzej Bajguz; Mohamed A. El-Sheikh; Parvaiz Ahmad (Environmental Pollution, 2023)

Comparison of constructed wetland performance coupled with aeration and tubesettler for pharmaceutical compound removal from hospital wastewater - Roohul Abad Khan; Nadeem A. Khan; Rachida El Morabet; Majed Alsubih; Amadur Rahman Khan; Saimah Khan; Muhammad Mubashir; Deepanraj Balakrishnan; Kuan Shiong Khoo (Environmental Research, 2023)

Assessing the genetic diversity in hawthorn (Crataegus spp.) genotypes using morphological, phytochemical and molecular markers - Ercan Yildiz; Ahmet Sümbül; Mehmet Yaman; Muhammad Azhar Nadeem; Ahmet Say; Faheem Shehzad Baloch; Gheorghe Cristian Popescu (Genetic Resources and Crop Evolution, 2023)

Impact of tourism development upon environmental sustainability: a suggested framework for sustainable ecotourism - Qadar Bakhsh Baloch; Syed Naseeb Shah; Nadeem Iqbal; Muhammad Sheeraz; Muhammad Asadullah; Sourath Mahar; Asia Umar Khan (Environmental Science and Pollution Research, 2023)

Do financial development, economic growth, energy consumption, and trade openness contribute to increase carbon emission in Pakistan? An insight based on ARDL bound testing approach - Muhammad Usman; Rakhshanda Kousar; Muhammad Sohail Amjad Makhdum; Muhammad Rizwan Yaseen; Abdul Majeed Nadeem (Environment, Development and Sustainability, 2023)

The alleviation of drought-induced damage to growth and physio-biochemical parameters of Brassica napus L. genotypes using an integrated approach of biochar amendment and PGPR application - Gul Lalay; Abd Ullah; Nadeem Iqbal; Ali Raza; Muhammad Ahsan Asghar; Sami Ullah (Environment, Development and Sustainability, 2022)
Drought is a major abiotic stress, affecting the metabolism, growth, and productivity of plants worldwide. Therefore, this study aimed/hypothesized to investigate the ameliorative effects of biochar and rhizobacteria in drought-damaged Brassica napus L. genotypes. The plants were divided into two groups based on the drought stress employment (15 days and 30 days). Both groups were then treated with PGPR, biochar, and their co-application, and the samples were taken from shoots and roots of both genotypes. Our results revealed that the drought resulted in a substantial decline in total flavonoids, phenolics, proteins, peroxidase (POD), superoxide dismutase (SOD), glutathione reductase (GR) as well as nutrient uptake in shoots and roots of both the studied genotypes. Contrarily, sugar and glycine betaine (GB) contents increased in both shoots and roots under drought stress conditions. However, the plants with co-application of biochar and PGPR showed better improvement of nutrient uptake, leaf relative water content (RWC), and growth parameters compared to drought-stressed, control, and the plants with sole biochar and PGPR application. In addition, the co-application of PGPR and biochar produced higher levels of sugar, proteins, flavonoids, phenolic compounds, and enzymatic activities (POD, SOD, GR, and dehydroascorbate reductase (DHAR)) than those that were not treated with biochar and PGPR or treated solely. Relative to Westar genotype, the Punjab sarson showed higher drought tolerance. In conclusion, we suggest that the co-application of biochar and PGPR can be an effective strategy for overcoming the drought-induced damage in plants. Graphical Abstract

DNA binding and cleavage, BRCA1 gene interaction, antiglycation and anticancer studies of transition metal complexes of sulfonamides - Arusa Akhtar; Muhammad Danish; Awais Asif; Muhammad Nadeem Arshad; Abdullah M. Asiri (Molecular Diversity, 2022)

Transition metal-doped SnO2 and graphene oxide (GO) supported nanocomposites as efficient photocatalysts and antibacterial agents - Tauseef Munawar; Muhammad Shahid Nadeem; Faisal Mukhtar; Muhammad Naveed ur Rehman; Muhammad Riaz; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Science and Pollution Research, 2022)

Cytotoxic and genotoxic evaluation of bisphenol S on onion root tips by Allium cepa and comet tests - Muhammad Muddassir Ali; Areej Fatima; Sadia Nawaz; Abdul Rehman; Maryam Javed; Asif Nadeem (Environmental Science and Pollution Research, 2022)

The central role of GmGLP20.4 in root architecture modifications of soybean under low-nitrogen stress - Wei Wang; Jiajia Li; Muhammad Nadeem; Jianxin Wang; Ru Huang; Qian Liu; Wenqiao Fan; Haowei Zheng; Long Yan; Xiaobo Wang (Theoretical and Applied Genetics, 2022)

Bisphenol S induced dysregulations in liver; iron regulatory genes and inflammatory mediators in male Wistar rats - Shazia Ghafoor; Muddasir Hassan Abbasi; Muhammad Babar Khawar; Asima Tayyeb; Tayyaba Saleem; Isbah Ashfaq; Nadeem Sheikh (Environmental Science and Pollution Research, 2022)

Revitalization of tourism and hospitality sector: preempting pandemics through lessons learned - Qadar Bakhsh Baloch; Sourath Maher; Syed Naseeb Shah; Muhammad Sheeraz; Nadeem Iqbal; Hassan Raza (Environmental Science and Pollution Research, 2022)

Complement C3a Receptor (C3aR) Mediates Vascular Dysfunction, Hippocampal Pathology, and Cognitive Impairment in a Mouse Model of VCID - Kanchan Bhatia; Adam Kindelin; Muhammad Nadeem; Mohammad Badruzzaman Khan; Junxiang Yin; Alberto Fuentes; Karis Miller; Gregory H. Turner; Mark C. Preul; Abdullah S. Ahmad; Elliott J. Mufson; Michael F. Waters; et al. (Translational Stroke Research, 2022)

Synthesis, characterization and biological evaluation of Bis-benzimidazolium salts and their silver(I)-N-heterocyclic carbene complexes - Rana Yasir Nadeem; Munazzah Yaqoob; WanSinn Yam; Rosenani A. Haque; Muhammad Adnan Iqbal (Medicinal Chemistry Research, 2022)

Light-emitting diodes induced in vitro regeneration of Alternanthera reineckii mini and validation via machine learning algorithms - Muhammad Aasim; Seyid Amjad Ali; Pınar Bekiş; Muhammad Azhar Nadeem (In Vitro Cellular & Developmental Biology - Plant, 2022)

Assessing Salt Tolerance Induction in Potato by Salicylic Acid Using Morpho-Physio-Biochemical, Ionic, and Yield Indices - Hafiz Nazar Faried; C. M. Ayyub; Fahad Masoud Wattoo; Mohsin Bashir; Kashif Razzaq; Gulzar Akhtar; Abid Hussain; Sami Ullah; Javed Iqbal Wattoo; Muhammad Amin; Shoaib Munir; Muhammad Rashid Shaheen; et al. (Potato Research, 2022)

Structural and Electronic (Absorption and Fluorescence) Properties of a Stable Triplet Diphenylcarbene: A DFT Study - Abrar Ul Hassan; Ayesha Mohyuddin; Sohail Nadeem; Cihat Güleryüz; Sadaf Ul Hassan; Mohsin Javed; Muhammad Salman Muhsan (Journal of Fluorescence, 2022)

Application of CSM-CANEGRO Model for Climate Change Impact Assessment and Adaptation for Sugarcane in Semi-arid Environment of Southern Punjab, Pakistan - Muhammad Nadeem; Muhammad Nazer Khan; Ghulam Abbas; Zartash Fatima; Pakeeza Iqbal; Mukhtar Ahmed; Muhammad Ali Raza; Abdul Rehman; Ehsan Ul Haq; Akbar Hayat; Muhammad Ali; Shakeel Ahmad (International Journal of Plant Production, 2022)

Freely dissolved organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) along the Indus River Pakistan: spatial pattern and risk assessment - Muhammad Sohail; Syed Ali Musstjab Akber Shah Eqani; Habib Bokhari; Muhammad Zaffar Hashmi; Nadeem Ali; Ambreen Alamdar; Joel E. Podgorski; Dave Adelman; Rainer Lohmann (Environmental Science and Pollution Research, 2022)

Potential of Fish Scale Biochar Nanocomposite with ZnO for Effective Sequestration of Cr (VI) from Water: Modeling and Kinetics - Azhar Ul Islam; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Qasim Kakar; Muhammad Nawaz; Muhammad Amjad; Saeed Ahmad Qaisrani; Muhammad Rizwan; Shafaqat Ali (International Journal of Environmental Research, 2022)

Recent progress in omics and biotechnological approaches for improved mango cultivars in Pakistan - Ghassan Zahid; Yıldız Aka Kaçar; Flavien Shimira; Sara Iftikhar; Muhammad Azhar Nadeem (Genetic Resources and Crop Evolution, 2022)

Lethal and sublethal effects of flonicamid (50 WG) and spirotetramat (240 SC) on Bemisia tabaci (Homoptera: Aleyrodidae): an age-stage two sex life table study - Aqsa Abbas; Javaid Iqbal; Ali Zeshan; Qurban Ali; Imran Nadeem; Humaira Malik; Tamsila Nazir; Muhammad Faheem Akhter; Bilal Bin Iqbal (Phytoparasitica, 2022)

Assessment of genetic diversity among 131 safflower (Carthamus tinctorius L.) accessions using peroxidase gene polymorphism (POGP) markers - Mehtap Yildiz; Muhammad Tanveer Altaf; Faheem Shehzad Baloch; Metin Koçak; Gökhan Sadık; Cansu Kuzğun; Muhammad Azhar Nadeem; Fawad Ali; Mehmet Bedir; Murat Tunçtürk (Molecular Biology Reports, 2022)

Energy-levels well-matched direct Z-scheme ZnNiNdO/CdS heterojunction for elimination of diverse pollutants from wastewater and microbial disinfection - Muhammad Shahid Nadeem; Tauseef Munawar; Faisal Mukhtar; Sana Batool; Murtaza Hasan; Usman Ali Akbar; Abbas Saeed Hakeem; Faisal Iqbal (Environmental Science and Pollution Research, 2022)

Leaf rolling dynamics for atmospheric moisture harvesting in wheat plant as an adaptation to arid environments - Sabah Merrium; Zulfiqar Ali; Muhammad Hammad Nadeem Tahir; Muhammad Habib-ur-Rahman; Sadia Hakeem (Environmental Science and Pollution Research, 2022)
Plant species surviving in the arid regions have developed novel leaf features to harvest atmospheric water. Before the collected water evaporates, it is absorbed and transported for storage within the tissues and move toward the root zone through the unique chemistry of leaf structures. Deep insights into such features reveal that similarities can be found in the wheat plant. Therefore, this study aimed to evaluate the leaf rolling dynamics among wheat genotypes and their relationships with moisture harvesting and its movement on the leaf surface. For this purpose, genotypes were characterized for leaf rolling at three distinct growth stages (tillering, booting, and spike emergence). The contact angle of leaf surface dynamics (adaxial and abaxial), water budget, and morphophysiological traits of genotypes were measured. The results indicate that leaf rolling varies from inward to twisting type among genotypes and positively affected the water use efficiency and soil moisture difference at all growth stages under normal and drought conditions. Results of wetting property (hydrophilic < 90°) of the leaf surface were positively associated with the atmospheric water collection (4–7 ml). The lower values of contact angle hysteresis (12–19°) also support this mechanism. Thus, genotypes with leaf rolling dynamics (inward rolled and twisted) and surface wettability is an efficient fog harvesting system in wheat for interception and utilization of fog water in drought-prone areas. These results can be exploited to develop self-irrigated and drought-tolerant crops.

Development of Optimized Sumatriptan–Prochlorperazine Combined Orodispersible Films Without Disintegrant: in vitro, ex vivo and in vivo Characterization - Sana Javed; Amjad Hussain; Pervaiz Akhtar Shah; Syed Atif Raza; Ubaid Ullah Anwer; Rahat Shamim; Fatima Rasool; Muhammad Ahsan Hafiz; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2022)

Pretreatment with Chitosan Arbitrates Physiological Processes and Antioxidant Defense System to Increase Drought Tolerance in Alfalfa (Medicago sativa L.) - Ghulam Mustafa; Muhammad Asif Shehzad; M. Hammad Nadeem Tahir; Fahim Nawaz; Gulzar Akhtar; Muhammad Asaad Bashir; Abdul Ghaffar (Journal of Soil Science and Plant Nutrition, 2022)

Ameliorative Effect of Silicic Acid and Silicates on Oxidative, Osmotic Stress, and Specific Ion Toxicity in Spring Wheat (Triticum aestivum L.) Genotypes - Muhammad Nadeem; Muhammad Anwar-ul-Haq; Muhammad Saqib; Muhammad Maqsood; Zhenli He (Journal of Soil Science and Plant Nutrition, 2022)

Phycoremediation of textile effluents with enhanced efficacy of biodiesel production by algae and potential use of remediated effluent for improving growth of wheat - Muhammad Rashid Waqas; Sajid Mahmood Nadeem; Muhammad Yahya Khan; Zeeshan Ahmad; Liaqat Ali; Hafiz Naeem Asghar; Azeem Khalid (Environmental Science and Pollution Research, 2022)

Assessment of cobalt in wheat grains as affected by diverse fertilizers: implications for public health - Abid Ejaz; Kafeel Ahmad; Zafar Iqbal Khan; Shahzad Akhtar; Razia Sultana; Muhammad Nadeem; Muhammad Iftikhar Hussain; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Inoculation of Azospirillum brasilense and exogenous application of trans-zeatin riboside alleviates arsenic induced physiological damages in wheat (Triticum aestivum) - Muhammad Saqlain Zaheer; Hafiz Haider Ali; Kehinde O. Erinle; Shabir Hussain Wani; Okon Godwin Okon; Muhammad Azhar Nadeem; Muhammad Nawaz; Muhammad Adnan Bodlah; Muhammad Mohsin Waqas; Javaid Iqbal; Ali Raza (Environmental Science and Pollution Research, 2022)

Assessment of cadmium and lead tolerance potential of quinoa (Chenopodium quinoa Willd) and its implications for phytoremediation and human health - Muhammad Amjad; Muhammad Mohsin Iqbal; Ghulam Abbas; Abu Bakar Umer Farooq; Muhammad Asif Naeem; Muhammad Imran; Behzad Murtaza; Muhammad Nadeem; Sven-Erik Jacobsen (Environmental Geochemistry and Health, 2022)

Serum Stable and Low Hemolytic Temporin-SHa Peptide Analogs Disrupt Cell Membrane of Methicillin-Resistant Staphylococcus aureus (MRSA) - Rukesh Maharjan; Arif Iftikhar Khan; Muhammad Nadeem-ul-Haque; Marc Maresca; M. Iqbal Choudhary; Farzana Shaheen; Shabana U. Simjee (Probiotics and Antimicrobial Proteins, 2022)

Applicability of inter-primer binding site iPBS- retrotransposon marker system for the assessment of genetic diversity and population structure of Peruvian rosewood (Aniba rosaeodora Ducke) germplasm - Faheem Shehzad Baloch; Stalin Juan Vasquez Guizado; Muhammad Tanveer Altaf; Ilker Yüce; Yeter Çilesiz; Mehmet Bedir; Muhammad Azhar Nadeem; Rustu Hatipoglu; Juan Carlos Castro Gómez (Molecular Biology Reports, 2022)

Effects of diverse irrigation with wastewater in soil and plants: assessing the risk of metal to the animal food chain - Zafar Iqbal Khan; Fatima Ghulam Muhammad; Kafeel Ahmad; Shahzad Akhtar; Muhammad Sohail; Muhammad Nadeem; Shahzadi Mahpara; Muhammad Umer Farooq Awan; Mona S. Alwahibi; Mohamed S. Elshikh; Muhammad Iftikhar Hussain (Environmental Science and Pollution Research, 2022)

Evaluation of nickel toxicity in wheat as function of diverse type of fertilizers: implications for public health - Abid Ejaz; Kafeel Ahmad; Zafar Iqbal Khan; Razia Sultana; Shahzad Akhtar; Muhammad Nadeem (Environmental Science and Pollution Research, 2022)

Does economic complexity matter for environmental sustainability? Using ecological footprint as an indicator - Muhammad Zahid Rafique; Abdul Majeed Nadeem; Wanjun Xia; Majid Ikram; Hafiz Muhammad Shoaib; Umer Shahzad (Environment, Development and Sustainability, 2022)

Applications of Biotechnology in Food and Agriculture: a Mini-Review - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Waseem Khalid; Hafiz Rehan Nadeem; Ghulam Mueen-ud-Din; Muhammad Zubair Khalid (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Drought-tolerant Bacillus megaterium isolated from semi-arid conditions induces systemic tolerance of wheat under drought conditions - Urooj Rashid; Humaira Yasmin; Muhammad Nadeem Hassan; Rabia Naz; Asia Nosheen; Muhammad Sajjad; Noshin Ilyas; Rumana Keyani; Zahra Jabeen; Saqib Mumtaz; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Plant Cell Reports, 2022)

Diagnostic, prognostic and therapeutic potential of long noncoding RNAs in cancer - Muhammad Babar Khawar; Syeda Eisha Hamid; Tayyba Jan; Muddasir Hassan Abbasi; Muhammad Idnan; Nadeem Sheikh (Molecular Biology Reports, 2022)

High-fat diet intake ameliorates the expression of hedgehog signaling pathway in adult rat liver - Rabia Mehmood; Nadeem Sheikh; Muhammad Babar Khawar; Muddasir Hassan Abbasi; Maryam Mukhtar (Molecular Biology Reports, 2022)

Systematic analysis of HD-ZIP transcription factors in sesame genome and gene expression profiling of SiHD-ZIP class I entailing drought stress responses at early seedling stage - Maryam Mehmood; Muhammad Jadoon Khan; Muhammad Jawad Khan; Nadeem Akhtar; Fizza Mughal; Syed Tahir Abbas Shah; Muhammad Zeeshan Hyder; Sumaira Farrakh; Irfan Sadiq (Molecular Biology Reports, 2022)

Nanocrystals: Characterization Overview, Applications in Drug Delivery, and Their Toxicity Concerns - Mohammed Asadullah Jahangir; Syed Sarim Imam; Abdul Muheem; Ananda Chettupalli; Fahad A. Al-Abbasi; Muhammad Shahid Nadeem; Imran Kazmi; Muhammad Afzal; Sultan Alshehri (Journal of Pharmaceutical Innovation, 2022)

Quantitative evaluation of zinc metal in meadows and ruminants for health assessment: implications for humans﻿ - Ayesha Maqsood; Zafar Iqbal Khan; Kafeel Ahmad; Shahzad Akhtar; Asma Ashfaq; Ifra Saleem Malik; Razia Sultana; Muhammad Nadeem; Jawaher Alkahtani; Yheni Dwiningsih; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Economic and financial impact of the COVID-19 pandemic in South Asia - Muhammad Azhar Khan; Hasnain Abbas Naqvi; Muhammad Mohsin Hakeem; Ghulam Moeen ud Din; Nadeem Iqbal (Environmental Science and Pollution Research, 2022)

Staged energy and water quality optimization for large water distribution systems - Muhammad Nadeem Sharif; Ezzeddin Bakhtavar; Husnain Haider; Guangji Hu; Kasun Hewage; Rehan Sadiq (Environmental Monitoring and Assessment, 2022)

Radiological risk assessment in sediment of Namal Lake, Mianwali, Pakistan - Irfan Afzal; Muhammad Zaman Chaudhary; Ehsan Ullah Khan; Tabassum Nasir; Nadeem Yaqoob (Environmental Monitoring and Assessment, 2022)

Effectiveness of exogenously applied chelated micronutrients for biofortification of wheat - Muhammad Imran Tipu; Muhammad Akhtar; Nadeem Sarwar; Saddam Hussain (Arabian Journal of Geosciences, 2022)

Anti-Huntington’s Effect of Butin in 3-Nitropropionic Acid-Treated Rats: Possible Mechanism of Action - Sultan Alshehri; Fahad A. Al-Abbasi; Mohammed M. Ghoneim; Syed Sarim Imam; Muhammad Afzal; Khalid Saad Alharbi; Muhammad Shahid Nadeem; Nadeem Sayyed; Imran Kazmi (Neurotoxicity Research, 2022)

New organosulfur metallic compounds as potent drugs: synthesis, molecular modeling, spectral, antimicrobial, drug likeness and DFT analysis - Abrar Ul Hassan; Sajjad Hussain Sumrra; Muhammad Nadeem Zafar; Muhammad Faizan Nazar; Ehsan Ullah Mughal; Muhammad Naveed Zafar; Mazhar Iqbal (Molecular Diversity, 2022)

Correction to: Bioaccumulation of lead in different varieties of wheat plant irrigated with wastewater in remote agricultural regions - Wuyi Liu; Asma Zafar; Zafar Iqbal Khan; Muhammad Nadeem; Kafeel Ahmad; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq (Environmental Science and Pollution Research, 2022)

A study on the contamination assessment, health risk and mobility of two heavy metals in the soil-plants-ruminants system of a typical agricultural region in the semi arid environment - Xiaoping Ge; Zafar Iqbal Khan; Fu Chen; Mubeen Akhtar; Kafeel Ahmad; Abid Ejaz; Muhammad Arslan Ashraf; Muhammad Nadeem; Shahzad Akhtar; Jawaher Alkahtani; Yheni Dwiningsih; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Does ICT diffusion lead to energy efficiency and environmental sustainability in emerging Asian economies? - Shufang Zhao; Muhammad Hafeez; Chaudhry Muhammad Nadeem Faisal (Environmental Science and Pollution Research, 2022)

Photocatalytic degradation of methylene blue using polyaniline-based silver-doped zinc sulfide (PANI-Ag/ZnS) composites - Sidra Mazhar; Umair Yaqub Qazi; Nimra Nadeem; Muhammad Zahid; Abdul Jalil; Fareeda Khan; Iftikhar Ul-Hasan; Imran Shahid (Environmental Science and Pollution Research, 2022)

Rice-associated antagonistic bacteria suppress the Fusarium fujikoroi causing rice bakanae disease - Mah-E-Neema Nawaz; Kamran Malik; Muhammad Nadeem Hassan (BioControl, 2022)

Ecological risk assessment of heavy metal chromium in a contaminated pastureland area in the Central Punjab, Pakistan: soils vs plants vs ruminants - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Nadeem; Shahid Mahmood; Muhammad Umar Farooq Awan; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Ayesha Maqsood; et al. (Environmental Science and Pollution Research, 2022)

Evaluation of potential ecological risk and prediction of zinc accumulation and its transfer in soil plants and ruminants: public health implications - Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Asma Ashfaq; Razia Sultana; Fatima Ghulam Muhammad; Ayesha Maqsood; Majida Naeem; Ifra Saleem Malik; Mudasra Munir; et al. (Environmental Science and Pollution Research, 2022)

Bioaccumulation and transfer of zinc in soil plant and animal system: a health risk assessment for the grazing animals - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Majida Naeem; Muhammad Nadeem; Jing Ma; Muhammad Umer Farooq Awan; Shahzadi Mahpara; Shahid Mehmood (Environmental Science and Pollution Research, 2022)

Multivariate Investigation of Toxic and Essential Metals in the Serum from Various Types and Stages of Colorectal Cancer Patients - Mian H. R. Mahmood; Muhammad Abdul Qayyum; Farhan Yaseen; Tahir Farooq; Zahid Farooq; Muhammad Yaseen; Ahmad Irfan; Khawaja Muddassir; Muhammad Nadeem Zafar; Muhammad Tariq Qamar; Arshad Mehmood Abbasi; Hai-Yang Liu (Biological Trace Element Research, 2022)

Economic assessment of water-saving irrigation management techniques and continuous flooded irrigation in different rice production systems - Muhammad Ishfaq; Nadeem Akbar; Usman Zulfiqar; Nauman Ali; Fahimuddin Shah; Shakeel Ahmad Anjum; Muhammad Farooq (Paddy and Water Environment, 2022)

Soil microbial biomass and extracellular enzyme–mediated mineralization potentials of carbon and nitrogen under long-term fertilization (> 30 years) in a rice–rice cropping system - Muhammad Nadeem Ashraf; Gao Jusheng; Wu Lei; Adnan Mustafa; Ahmed Waqas; Tariq Aziz; Waqas-ud-Din Khan; Shafeeq-ur-Rehman; Babar Hussain; Muhammad Farooq; Zhang Wenju; Xu Minggang (Journal of Soils and Sediments, 2021)

Facile synthesis, spectroscopic evaluation and antimicrobial screening of metal endowed triazole compounds - Sajjad H. Sumrra; Wardha Zafar; Hassan Javed; Muddassar Zafar; Muhammad Z. Hussain; Muhammad Imran; Muhammad A. Nadeem (BioMetals, 2021)

Assessment of Microscopic Detection of Malaria with Nested Polymerase Chain Reaction in War-Torn Federally Administered Tribal Areas of Pakistan - Muhammad Faisal Nadeem; Aamer Ali Khattak; Nadia Zeeshan; Usman Ayub Awan; Adnan Yaqoob (Acta Parasitologica, 2021)

Essential oil composition and antibacterial activity of Canarium strictum Roxb. resin - Halima Tahir; Nadeem Muhammad; Azeem Intisar; Muhammad Imran Din; Uzma Qaisar; Muhammad Abdul Qadir; Noor Ul Ain; Zeeshan Ahmad; Pakeeza Aziz; Muhammad Khurram Shahzad; Irshad Hussain (Plant Biosystems, 2021)

Constituents and antibacterial activity of leaf essential oil of Plectranthus scutellarioides - Pakeeza Aziz; Nadeem Muhammad; Azeem Intisar; Muhammad Amin Abid; Muhammad Imran Din; Muhammad Yaseen; Rehana Kousar; Aqsa Aamir; Quratulain; Rabia Ejaz (Plant Biosystems, 2021)

Isolation and identification of low-density polyethylene degrading novel bacterial strains - Habibullah Nadeem; Khush Bakhat Alia; Faizan Muneer; Ijaz Rasul; Muhammad Hussnain Siddique; Farrukh Azeem; Muhammad Zubair (Archives of Microbiology, 2021)

Preparation and Characterization of pH-Independent Sustained-Release Tablets Containing Hot Melt Extruded Solid Dispersions of Clarithromycin - Qazi Amir Ijaz; Sumera Latif; Qurat-ul-ain Shoaib; Memoona Rashid; Muhammad Sohail Arshad; Amjad Hussain; Nadeem Irfan Bukhari; Sohail Riaz; Nasir Abbas (AAPS PharmSciTech, 2021)

Satires, narratives and journalistic divides: Discourses on free speech in Western and Islamic news media - Muhammad Khalil Khan; Fei Wu; Cornelius B. Pratt; Nadeem Akhtar (The Social Science Journal, 2021)

Deciphering the genetic diversity and population structure of Turkish bread wheat germplasm using iPBS-retrotransposons markers - Muhammad Azhar Nadeem (Molecular Biology Reports, 2021)

High-fat diet-induced splenic, hepatic, and skeletal muscle architecture damage: cellular and molecular players - Ambreen Asghar; Tasleem Akhtar; Tayyeba Batool; Muhammad Babar Khawar; Sania Nadeem; Rabia Mehmood; Nadeem Sheikh (Molecular and Cellular Biochemistry, 2021)

Strigolactone (GR24) Induced Salinity Tolerance in Sunflower (Helianthus annuus L.) by Ameliorating Morpho-Physiological and Biochemical Attributes Under In Vitro Conditions - Hira Zulfiqar; Muhammad Shahbaz; Muhammad Ahsan; Muhammad Nafees; Hammad Nadeem; Muhammad Akram; Ambreen Maqsood; Sunny Ahmar; Muhammad Kamran; Saud Alamri; Manzer H. Siddiqui; Shah Saud; et al. (Journal of Plant Growth Regulation, 2021)

Evaluation of pasture allowance of manganese for ruminants - Xiaoping Ge; Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Mudasra Munir; Muhammad Nadeem; Muhammad Umer Farooq Awan; et al. (Environmental Science and Pollution Research, 2021)

Severity of zinc and iron malnutrition linked to low intake through a staple crop: a case study in east-central Pakistan - Muhammad Ishfaq; Abdul Wakeel; Muhammad Nadeem Shahzad; Aysha Kiran; Xuexian Li (Environmental Geochemistry and Health, 2021)

Biotechnological approaches in agriculture and environmental management - bacterium Kocuria rhizophila 14ASP as heavy metal and salt- tolerant plant growth- promoting strain - Muhammad Siddique Afridi; Jonathan d. Van Hamme; Jochen Bundschuh; Sumaira; Muhammad Nadeem Khan; Abdul Salam; Muhammad Waqar; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Biologia, 2021)

Remote Ischemic Post-Conditioning Therapy is Protective in Mouse Model of Traumatic Optic Neuropathy - Muhammad Nadeem; Adam Kindelin; Laura Mahady; Kanchan Bhatia; Md Nasrul Hoda; Andrew F. Ducruet; Saif Ahmad (NeuroMolecular Medicine, 2021)

Helminth protection against type-1 diabetes: an insight into immunomodulatory effect of helminth-induced infection - Muhammad Adnan Sabir Mughal; Muhammad Kasib Khan; Zaheer Abbas; Rao Zahid Abbas; Hammad ur Rehman Bajwa; Abdullah Khalid Chatha; Muhammad Imran; Zia ud Din Sindhu; Asghar Abbas; Arsalan Zafar; Muhammad Nadeem (Molecular Biology Reports, 2021)

Exploring the genetic diversity and population structure of scarlet eggplant germplasm from Rwanda through iPBS-retrotransposon markers - Flavien Shimira; Hatice Filiz Boyaci; Yeter Çilesiz; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Hatıra Taşkin (Molecular Biology Reports, 2021)

Environmental friendly extraction of walnut bark-based juglone natural colorant for dyeing studies of wool fabric - Waseem-ul- Arifeen; Fazal-Ur- Rehman; Shahid Adeel; Muhammad Zuber; Mirza Nadeem Ahmad; Tanvir Ahmad (Environmental Science and Pollution Research, 2021)

An in vitro antiviral activity of iodine complexes against SARS-CoV-2 - Imran Altaf; Muhammad Faisal Nadeem; Nadir Hussain; Muhammad Nawaz; Sohail Raza; Muhammad Abu bakr Shabbir; Muhammad Adnan Ashraf; Muhammad Asad Ali; Sohail Hassan; Muhammad Waqar Aziz; Nazish Matti; Muhammad Ashraf; et al. (Archives of Microbiology, 2021)

Correction to: Bacillus subtilis Y16 and biogas slurry enhanced potassium to sodium ratio and physiology of sunflower (Helianthus annuus L.) to mitigate salt stress - Samina Hamid; Iftikhar Ahmad; Muhammad Javed Akhtar; Muhammad Nadeem Iqbal; Muhammad Shakir; Muhammad Tahir; Atta Rasool; Annum Sattar; Mahreen Khalid; Allah Ditta; Bo Zhu (Environmental Science and Pollution Research, 2021)

Sunlight-induced photocatalytic degradation of various dyes and bacterial inactivation using CuO–MgO–ZnO nanocomposite - Tauseef Munawar; Faisal Mukhtar; Sadaf Yasmeen; Muhammad Naveed-ur-Rehman; Muhammad Shahid Nadeem; Muhammad Riaz; Muhammad Mansoor; Faisal Iqbal (Environmental Science and Pollution Research, 2021)

Appraisal of iron accumulation in soil, forages, and blood plasma of sheep and goats: a case study in different districts of Punjab, Pakistan - Zafar Iqbal Khan; Kafeel Ahmad; Samra Siddique; Kinza Wajid; Humayun Bashir; Muhammad Nadeem; Muhammad Fiaz Qamar; Muhammad Fahad Ullah; Saif Ur Rehman (Environmental Science and Pollution Research, 2021)

Bacillus subtilis Y16 and biogas slurry enhanced potassium to sodium ratio and physiology of sunflower (Helianthus annuus L.) to mitigate salt stress - Samina Hamid; Iftikhar Ahmad; Muhammad Javed Akhtar; Muhammad Nadeem Iqbal; Muhammad Shakir; Muhammad Tahir; Atta Rasool; Annum Sattar; Mahreen Khalid; Allah Ditta; Bo Zhu (Environmental Science and Pollution Research, 2021)

Evaluation of transfer of lead in soil plant animal system: assessment of consequences of its toxicity - Fu Chen; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Tasneem Ahmad; Ifra Saleem Malik; Asma Ashfaq; Mudasra Munir; Sonaina Nazar; Zunaira Munir; Abid Ejaz; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

COVID-19 transmission, vulnerability, persistence and nanotherapy: a review - Afzal Husain Khan; Vineet Tirth; Manal Fawzy; Alaa El Din Mahmoud; Nadeem A. Khan; Sirajuddin Ahmed; Syed Sadat Ali; Muhammad Akram; Leena Hameed; Saiful Islam; Gotam Das; Sharmili Roy; et al. (Environmental Chemistry Letters, 2021)

Correction to: Assessing the socio-economic viability of solar commercialization and electrification in south Asian countries - Huaping Sun; Rehmat Ullah Awan; Muhammad Atif Nawaz; Muhammad Mohsin; Abdul Khaliq Rasheed; Nadeem Iqbal (Environment, Development and Sustainability, 2021)

Genetic dissection of days to flowering via genome-wide association studies in Turkish common bean germplasm - Muhammad Azhar Nadeem; Ephrem Habyarimana; Tolga Karaköy; Faheem Shehzad Baloch (Physiology and Molecular Biology of Plants, 2021)

Impact of economic capabilities and population agglomeration on PM2.5 emission: empirical evidence from sub-Saharan African countries - Summaira Malik; Asim Iqbal; Asma Imran; Muhammad Usman; Muhammad Nadeem; Saira Asif; Awais Bokhari (Environmental Science and Pollution Research, 2021)

Assessing the socio-economic viability of solar commercialization and electrification in south Asian countries - Huaping Sun; Rehmat Ullah Awan; Muhammad Atif Nawaz; Muhammad Mohsin; Abdul Khaliq Rasheed; Nadeem Iqbal (Environment, Development and Sustainability, 2021)

Drought Tolerance Strategies in Plants: A Mechanistic Approach - Muhammad Ilyas; Mohammad Nisar; Nadeem Khan; Ali Hazrat; Aamir Hamid Khan; Kashif Hayat; Shah Fahad; Aziz Khan; Abid Ullah (Journal of Plant Growth Regulation, 2021)

Correction to: Monitoring of copper accumulation in water, soil, forage, and cows impacted by heavy automobiles - Tasneem Ahmad; Sonaina Nazar; Kafeel Ahmad; Zafar Iqbal Khan; Humayun Bashir; Asma Ashfaq; Mudasra Munir; Zunaira Munir; Khadim Hussain; Jawaher Alkahtani; Mohamed Soliman Elshikh; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

Impact of stock market, renewable energy consumption and urbanization on environmental degradation: new evidence from BRICS countries - Ijaz Younis; Aziza Naz; Syed Ahsan Ali Shah; Muhammad Nadeem; Cheng Longsheng (Environmental Science and Pollution Research, 2021)

Monitoring of copper accumulation in water, soil, forage, and cows impacted by heavy automobiles in Sargodha, Pakistan - Tasneem Ahmad; Sonaina Nazar; Kafeel Ahmad; Zafar Iqbal Khan; Humayun Bashir; Asma Ashfaq; Mudasra Munir; Zunaira Munir; Khadim Hussain; Jawaher Alkahtani; Mohamed Soliman Elshikh; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

Comparative efficacy of biogenic zinc oxide nanoparticles synthesized by Pseudochrobactrum sp. C5 and chemically synthesized zinc oxide nanoparticles for catalytic degradation of dyes and wastewater treatment - Khadija Siddique; Muhammad Shahid; Tanvir Shahzad; Faisal Mahmood; Habibullah Nadeem; Muhammad Saif ur Rehman; Sabir Hussain; Omer Sadak; Sundaram Gunasekaran; Tahseen Kamal; Ikram Ahmad (Environmental Science and Pollution Research, 2021)

Socioeconomic impacts of domestic biogas plants on rural households to strengthen energy security - Nadeem Iqbal; Muhammad Arshad Sakhani; Abdul Razzaq Khan; Atiq-ur-Rehman; Zahid Ajmal; Muhammad Zubair Khan (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: Evaluation of toxicity potential of cobalt in wheat irrigated with wastewater: health risk implications for public - Fu Chen; Zafar Iqbal Khan; Asma Zafar; Jing Ma; Muhammad Nadeem; Kafeel Ahmad; Shehzadi Mahpara; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; et al. (Environmental Science and Pollution Research, 2021)

Growth and Physiology of Maize (Zea mays L.) in a Nickel-Contaminated Soil and Phytoremediation Efficiency Using EDTA - Muhammad Imran Tipu; Muhammad Yasin Ashraf; Nadeem Sarwar; Muhammad Akhtar; Muhammad Rashid Shaheen; Sajjad Ali; Christos A. Damalas (Journal of Plant Growth Regulation, 2021)

Overcoming open defecation for healthier environment in case of Pakistan - Muhammad Irfan Malik; Shahzada Muhammad Naeem Nawaz; Muhammad Nadeem (Environmental Science and Pollution Research, 2021)

Relative Effectiveness of Phosphorus and Potassium Along with Compost and Organic Acids on Maize Crop Grown in Calcareous Soil: a Multivariate Analysis - Saira Tabbasum; Muhammad Akhtar; Nadeem Sarwar; Muhammad Imran Tipu; Wasiq Ikram; Arooba Ashraf; Amjad Ejaz; Behzad Murtaza; Muhammad Rizwan Khan (Journal of Soil Science and Plant Nutrition, 2021)

Influence of Nitrogen Fertilization Pattern on Productivity, Nitrogen Use Efficiencies, and Profitability in Different Rice Production Systems - Muhammad Ishfaq; Nadeem Akbar; Usman Zulfiqar; Nauman Ali; Khawar Jabran; Mohsin Nawaz; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2021)

Arsenic and lead in the indoor residential settings of different socio-economic status; assessment of human health risk via dust exposure - Nadeem Ali; Syed Ali Musstjab Akber Shah Eqani; Ehtisham Nazar; Nabil A. Alhakamy; Muhammad Imtiaz Rashid; Khurram Shahzad; Jahan Zeb; Heqing Shen; Iqbal Mohammad Ibrahim Ismail; Hussain Mohammed Salem Ali Albar (Environmental Science and Pollution Research, 2021)

Appraisal of chromium in chicken reared on maize irrigated with sewage water - Zill-e-Huma; Zafar Iqbal Khan; Ijaz Rasool Noorka; Kafeel Ahmad; Kinza Wajid; Muhammad Nadeem; Mudasra Munir; Ifra Saleem Malik; Madiha Kiran; Tahir Hussain; Muhammad F. Qamar; Tasneem Ahmad; et al. (Environmental Science and Pollution Research, 2021)

Managerial policy and economic analysis of wind-generated renewable hydrogen for light-duty vehicles: Green solution of energy crises - Jingyi Liu; Qaiser Abbas; Majed Alharthi; Muhammad Mohsin; Farhat Rasul; Nadeem Iqbal (Environmental Science and Pollution Research, 2021)

Physicomechanical, stability, and pharmacokinetic evaluation of aceclofenac dimethyl urea cocrystals - Hafsa Afzal; Nasir Abbas; Amjad Hussain; Sumera Latif; Kanwal Fatima; Muhammad Sohail Arshad; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2021)

Pattern of Trace Metal Uptake in Pearl Millet as a Result of Application of Organic and Synthetic Fertilizers - Kinza Wajid; Kafeel Ahmad; Zafar Iqbal Khan; Muhammad Nadeem (International Journal of Environmental Research, 2021)

Organoid culture to study epithelial cell differentiation and barrier formation in the colon: bridging the gap between monolayer cell culture and human subject research - James Varani; Shannon D. McClintock; Muhammad Nadeem Aslam (In Vitro Cellular & Developmental Biology - Animal, 2021)

Assessing the perceived impact of exploration and production of hydrocarbons on households perspective of environmental regulation in Ghana - David Ajene Alemzero; Nadeem Iqbal; Sajid Iqbal; Muhammad Mohsin; Ngonadi Josiah Chukwuma; Burhan Ali Shah (Environmental Science and Pollution Research, 2021)

Correction to: Appraisal of chromium in chicken reared on maize irrigated with sewage water - Zill-e-Huma; Zafar Iqbal Khan; Ijaz Rasool Noorka; Kafeel Ahmad; Kinza Wajid; Muhammad Nadeem; Mudasra Munir; Ifra Saleem Malik; Madiha Kiran; Tahir Hussain; Muhammad F. Qamar; Tasneem Ahmad; et al. (Environmental Science and Pollution Research, 2021)

Bioaccumulation of cadmium in different genotypes of wheat crops irrigated with different sources of water in agricultural regions - Asma Zafar; Zafar Iqbal Khan; Wuyi Liu; Humayun Bashir; Kafeel Ahmad; Kinza Wajid; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Muhammad Nadeem; Tasneem Ahmad; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2021)

Assessing energy security in Africa based on multi-dimensional approach of principal composite analysis - David Ajene Alemzero; Huaping Sun; Muhammad Mohsin; Nadeem Iqbal; Muhammad Nadeem; Xuan Vinh Vo (Environmental Science and Pollution Research, 2021)

Zinc Application in Combination with Zinc Solubilizing Enterobacter sp. MN17 Improved Productivity, Profitability, Zinc Efficiency, and Quality of Desi Chickpea - Aman Ullah; Muhammad Farooq; Faisal Nadeem; Abdul Rehman; Mubshar Hussain; Ahmad Nawaz; Muhammad Naveed (Journal of Soil Science and Plant Nutrition, 2020)

Comparative Response of Two Rice (Oryza sativa L.) Cultivars to Applied Zinc and Manganese for Mitigation of Salt Stress - Faisal Nadeem; Muhammad Azhar; Muhammad Anwar-ul-Haq; Muhammad Sabir; Tayyaba Samreen; Abdullah Tufail; Hafiz Umair Masood Awan; Wu Juan (Journal of Soil Science and Plant Nutrition, 2020)

Landslides assessment using geophysical and passive radon exhalation detection techniques in Murree Hills, northern Pakistan: Implication for environmental hazard assessment - Khawar Ashfaq Ahmed; Sarfraz Khan; Mahmood Sultan; Umair Bin Nisar; Muhammad Rizwan Mughal; Shahid Nadeem Qureshi (Journal of Earth System Science, 2020)

Correction to: A study on the transfer of chromium from meadows to grazing livestock: an assessment of health risk - Zafar Iqbal Khan; Kafeel Ahmad; Samra Siddique; Tasneem Ahmad; Humayun Bashir; Mudasra Munir; Shahzadi Mahpara; Ifra Saleem Malik; Kinza Wajid; Ilker Ugulu; Muhammad Nadeem; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2020)

Environmental toxicology and associated human health risks - Muhammad Shahid; Muhammad Nadeem; Hafiz Faiq Bakhat (Environmental Science and Pollution Research, 2020)

Single tube multiplex PCR assay for the identification of banned meat species - Memoona Iqbal; Muhammad Sulyman Saleem; Muhammad Imran; Waseem Ahmad Khan; Kamran Ashraf; M. Yasir Zahoor; Imran Rashid; Habib-Ur Rehman; Asif Nadeem; Saadat Ali; Sarwat Naz; Wasim Shehzad (Food Additives & Contaminants Part B-Surveillance, 2020)

Statistical Assessment of Toxic and Essential Metals in the Serum of Female Patients with Lung Carcinoma from Pakistan - Muhammad Abdul Qayyum; Zahid Farooq; Muhammad Yaseen; Mian HR Mahmood; Ahmad Irfan; Muhammad Nadeem Zafar; Muddassir Khawaja; Kashif Naeem; Dursun Kisa (Biological Trace Element Research, 2020)

Biofortification with Zinc and Iron Improves the Grain Quality and Yield of Wheat Crop - Yasir Ramzan; Muhammad Bilal Hafeez; Shahbaz Khan; Majid Nadeem; Saleem-ur-Rahman; Sumaira Batool; Javed Ahmad (International Journal of Plant Production, 2020)

RETRACTED ARTICLE: Trilemma assessment of energy intensity, efficiency, and environmental index: evidence from BRICS countries - Zulifqar Ali Baloch; Qingmei Tan; Nadeem Iqbal; Muhammad Mohsin; Qaiser Abbas; Wasim Iqbal; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Effective sequestration of Cr (VI) from wastewater using nanocomposite of ZnO with cotton stalks biochar: modeling, kinetics, and reusability - Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Hussnain Siddique; Zafar Iqbal; Muhammad Amjad; Muhammad Rizwan; Shafaqat Ali (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: Matrine alleviates neurobehavioral alterations via modulation of JNK-mediated caspase-3 and BDNF/VEGF signaling in a mouse model of burn injury - Adnan Khan; Bushra Shal; Muhammad Naveed; Bakht Nasir; Nadeem Irshad; Hussain Ali; Salman Khan (Psychopharmacology, 2020)

Soil and microbial biomass stoichiometry regulate soil organic carbon and nitrogen mineralization in rice-wheat rotation subjected to long-term fertilization - Muhammad Nadeem Ashraf; Cheng Hu; Lei Wu; Yinghua Duan; Wenju Zhang; Tariq Aziz; Andong Cai; Muhammad Mohsin Abrar; Minggang Xu (Journal of Soils and Sediments, 2020)

Bioaccumulation of lead in different varieties of wheat plant irrigated with wastewater in remote agricultural regions - Wuyi Liu; Asma Zafar; Zafar Iqbal Khan; Muhammad Nadeem; Kafeel Ahmad; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq (Environmental Science and Pollution Research, 2020)

Cadmium Partitioning, Physiological and Oxidative Stress Responses in Marigold (Calendula calypso) Grown on Contaminated Soil: Implications for Phytoremediation - Amjad Farooq; Muhammad Nadeem; Ghulam Abbas; Arslan Shabbir; Muhammad Shafique Khalid; Hafiz Muhammad Rashad Javeed; Muhammad Farhan Saeed; Ahsan Akram; Adnan Younis; Gulzar Akhtar (Bulletin of Environmental Contamination and Toxicology, 2020)

A study on the transfer of chromium from meadows to grazing livestock: an assessment of health risk - Zafar Iqbal Khan; Kafeel Ahmad; Samra Siddique; Tasneem Ahmad; Humayun Bashir; Mudasra Munir; Shahzadi Mahpara; Ifra Saleem Malik; Kinza Wajid; Ilker Ugulu; Muhammad Nadeem; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2020)

Microbial l-asparaginase: purification, characterization and applications - Faizan Muneer; Muhammad Hussnain Siddique; Farrukh Azeem; Ijaz Rasul; Saima Muzammil; Muhammad Zubair; Muhammad Afzal; Habibullah Nadeem (Archives of Microbiology, 2020)

Extracting mass concentration time series features for classification of indoor and outdoor atmospheric particulates - Lal Hussain; Wajid Aziz; Sharjil Saeed; Muhammad Rafique; Malik Sajjad Ahmed Nadeem; Seong-O Shim; Sania Aftar; Jawad-ur-Rehman Pirzada (Acta Geophysica, 2020)

Comparative analysis of oil composition and antibacterial activity of aerial parts of Terminalia arjuna (Roxb.) - Shehar Bano; Azeem Intisar; Mahd Rauf; Abdul Ghaffar; Farhat Yasmeen; Waheed-Uz- Zaman; Uzma Intisar; Gulnaz Kausar; Nadeem Muhammad; Aqsa Aamir (Natural Product Research, 2020)

Genome-wide association study identifies various loci underlying agronomic and morphological traits in diversified potato panel - Muhammad Abu Bakar Zia; Ufuk Demirel; Muhammad Azhar Nadeem; Mehmet Emin Çaliskan (Physiology and Molecular Biology of Plants, 2020)

First report of cucurbit aphid borne yellows virus (CABYV) infecting melon in Pakistan - Muhammad Ahsan; Muhammad Ashfaq; Tariq Mukhtar; Nadeem Akhtar Abbasi; Zohaib Asad (Journal of Plant Pathology, 2020)

A study on the seasonal transfer of two metals from pasture to animals: health risk assessment - Zafar Iqbal Khan; Mubeen Akhtar; Kafeel Ahmad; Asma Ashfaq; Muhammad Nadeem; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik (Environmental Science and Pollution Research, 2020)

Relationship between inward FDI and environmental degradation for Pakistan: an exploration of pollution haven hypothesis through ARDL approach - Abdul M. Nadeem; Tariq Ali; Muhammad T. I. Khan; Zhengquan Guo (Environmental Science and Pollution Research, 2020)

A forecasting model approach of sustainable electricity management by developing adaptive neuro-fuzzy inference system - Aamir Nawaz Khan; Muhammad Asif Nadeem; Muhammad Shahid Hussain; Muhammad Aslam; Aqeel Ahmed Bazmi (Environmental Science and Pollution Research, 2020)

Effect of Organic Manure and Mineral Fertilizers on Bioaccumulation and Translocation of Trace Metals in Maize - Kinza Wajid; Kafeel Ahmad; Zafar Iqbal Khan; Muhammad Nadeem; Humayun Bashir; Fu Chen; Ilker Ugulu (Bulletin of Environmental Contamination and Toxicology, 2020)

Impact of financial development on CO2 emissions: A comparative analysis of developing countries (D8) and developed countries (G8) - Hafiz Muhammad Shoaib; Muhammad Zahid Rafique; Abdul Majeed Nadeem; Shaoan Huang (Environmental Science and Pollution Research, 2020)

Molecular characterization of genetic diversity and similarity centers of safflower accessions with ISSR markers - Fawad Ali; Muhammad Azhar Nadeem; Ephrem Habyarimana; Abdurrahim Yılmaz; Muhammad Amjad Nawaz; Iftikhar Hussain Khalil; Sezai Ercişli; Gyuhwa Chung; Hassan Javed Chaudhary; Faheem Shehzad Baloch (Brazilian Journal of Botany, 2020)

Linking traditional anti-ulcer use of rhizomes of Bergenia ciliata (Haw.) to its anti-Helicobacter pylori constituents - Ejaz Ali; Najma Arshad; Nadeem Irfan Bukhari; Muhammad Nawaz Tahir; Shamail Zafar; Amjad Hussain; Sajida Parveen; Shaista Qamar; Naureen Shehzadi; Khalid Hussain (Natural Product Research, 2020)

Fabrication and Characterization of Thiolated Chitosan Microneedle Patch for Transdermal Delivery of Tacrolimus - Zulcaif Ahmad; Muhammad Imran Khan; Muhammad Irfan Siddique; Hafiz Shoaib Sarwar; Gul Shahnaz; Syed Zajif Hussain; Nadeem Irfan Bukhari; Irshad Hussain; Muhammad Farhan Sohail (AAPS PharmSciTech, 2020)

In Vivo Evaluation of a Novel Chitosan-Polycaprolactone Based Mucoadhesive Gastro-Retentive Sustained Release Drug Delivery System for Milnacipran HCl - Talib Hussain; Muhammad Ijaz; Rahat Shamim; Khalid Hussain; Nasir Abbas; Amjad Hussain; Julia Anita Griessinger; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2020)

Correction to: Characterization, the Antioxidant and Antimicrobial Activity of Exopolysaccharide Isolated from Poultry Origin Lactobacilli - Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; Hafiz Fakhar Hayat; Nazim Hussain; Sobia Sarwar; Humaira Aslam; Ahmad Nadeem; Junling Shi (Probiotics and Antimicrobial Proteins, 2019)

Characterization, the Antioxidant and Antimicrobial Activity of Exopolysaccharide Isolated from Poultry Origin Lactobacilli - Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; Hafiz Fakhar Hayat; Nazim Hussain; Sobia Sarwar; Humaira Aslam; Ahmad Nadeem; Junling Shi (Probiotics and Antimicrobial Proteins, 2019)

The Effect of Encapsulation on The Stability of Probiotic Bacteria in Ice Cream and Simulated Gastrointestinal Conditions - Muhammad Afzaal; Farhan Saeed; Muhammad Umair Arshad; Muhammad Tahir Nadeem; Muhammad Saeed; Tabussam Tufail (Probiotics and Antimicrobial Proteins, 2019)

Probing the effect of various lipids and polymer blends on clopidogrel encapsulated floating microcarriers - Saba Irshad; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Nadeem Sabir; Adnan Ali; Ahmad Nawaz Khan; Abid Mehmood Yousaf; Talib Hussain; Yasser Shahzad (DARU Journal of Pharmaceutical Sciences, 2019)

DNA barcoding of Haplophyllum gilesii (Hemsel.) C. C. Townsend from the Gilgit-Baltistan Province of Pakistan - Bushra Khan; Habib Ahmad; Jan Alam; Muhammad Shahid Nadeem; Aziz Ud-Din; Inam Ullah; Shafee Ur Rehman; Khushi Muhammad (Brazilian Journal of Botany, 2019)

Thidiazuron-induced efficient biosynthesis of phenolic compounds in callus culture of Ipomoea turbinata Lagasca and Segura - Waqar Ahmad; Adnan Zahir; Muhammad Nadeem; Muhammad Zia; Christophe Hano; Bilal Haider Abbasi (In Vitro Cellular & Developmental Biology - Plant, 2019)

Circulation of multiple subtypes (A, G and CRFs 02_AG) of human immunodeficiency virus type 1 (HIV-1) in selected districts of Punjab province, Pakistan - Saima Yaqub; Tahir Yaqub; Muhammad Zubair Shabbir; Asif Nadeem; Nadia Mukhtar; Firnas Ata Ur Rehman; Aziz-ul Rahman; Muhammad Furqan Shahid; Muzaffar Ali; Tayyebah Sohail; Zarfishan Tahir (Archives of Virology, 2019)

Integrated effect of energy consumption, economic development, and population growth on CO2 based environmental degradation: a case of transport sector - Muhammad Mohsin; Qaiser Abbas; Jijian Zhang; Muhammad Ikram; Nadeem Iqbal (Environmental Science and Pollution Research, 2019)

Selection of CMIP5 multi-model ensemble for the projection of spatial and temporal variability of rainfall in peninsular Malaysia - Muhammad Noor; Tarmizi bin Ismail; Shamsuddin Shahid; Kamal Ahmed; Eun-Sung Chung; Nadeem Nawaz (Theoretical and Applied Climatology, 2019)

Zinc biofortification of cereals—role of phosphorus and other impediments in alkaline calcareous soils - Muhammad Akhtar; Sundas Yousaf; Nadeem Sarwar; Saddam Hussain (Environmental Geochemistry and Health, 2019)

Assessment of nematodes in Punjab Urial (Ovis vignei punjabiensis) population in Kalabagh Game Reserve: development of a DNA barcode approach - Amna Arshad Bajwa; Jordan Patrick Cuff; Muhammad Imran; Saher Islam; Riffat Mansha; Kamran Ashraf; Arman Khan; Muhammad Imran Rashid; Muhammad Yasir Zahoor; Waseem Ahmad Khan; Habib Ur Rehman; Asif Nadeem; et al. (European Journal of Wildlife Research, 2019)

Evaluation of toxic potential of metals in wheat crop grown in wastewater-contaminated soil in Punjab, Pakistan - Zafar Iqbal Khan; Kafeel Ahmad; Fauzia Batool; Kinza Wajid; Naunain Mehmood; Asma Ashfaq; Humayun Bashir; Muhammad Nadeem; Saif Ullah (Environmental Science and Pollution Research, 2019)

Synthesis of magnetite-based nanocomposites for effective removal of brilliant green dye from wastewater - Muhammad Imran; Azhar Ul Islam; Muhammad Adnan Tariq; Muhammad Hussnain Siddique; Noor Samad Shah; Zia Ul Haq Khan; Muhammad Amjad; Salah Ud Din; Ghulam Mustafa Shah; Muhammad Asif Naeem; Muhammad Nadeem; Muhammad Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Management of hyperuricemia through dietary polyphenols as a natural medicament: A comprehensive review - Arshad Mehmood; Lei Zhao; Chengtao Wang; Muhammad Nadeem; Ali Raza; Nawazish Ali; Amjad Abbas Shah (Critical Reviews in Food Science and Nutrition, 2019)

Toxicological potential of cobalt in forage for ruminants grown in polluted soil: a health risk assessment from trace metal pollution for livestock - Zafar Iqbal Khan; Nimra Arshad; Kafeel Ahmad; Muhammad Nadeem; Asma Ashfaq; Kinza Wajid; Humayun Bashir; Mudasra Munir; Bushra Huma; Hafsa Memoona; Madiha Sana; Khalid Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Role of phosphorous mining in mobilization and bioaccessibility of heavy metals in soil-plant system: Abbottabad, Pakistan - Afshan; Sajjad Ahmad; Muhammad Imran; Rab Nawaz; Muhammad Arshad; Muhammad Ejaz Ul Islam Dar; Muhammad Hussnain Siddque; Muhammad Nadeem; Liaqat Ali (Arabian Journal of Geosciences, 2019)

Glucanolytic Rhizobacteria Produce Antifungal Metabolites and Elicit ROS Scavenging System in Sugarcane - Muhammad Atif Zia; Humaira Yasmin; Faluk Shair; Zahra Jabeen; Saqib Mumtaz; Zafar Hayat; Syed Zia ul Husnain Shah; Shahid Afghan; Fauzia Yusuf Hafeez; Muhammad Nadeem Hassan (Sugar Tech, 2019)

Potential treatment of atopic dermatitis: tolerability and safety of cream containing nanoparticles loaded with hydrocortisone and hydroxytyrosol in human subjects - Muhammad Irfan Siddique; Haliza Katas; Adawiyah Jamil; Mohd Cairul Iqbal Mohd Amin; Shiow-Fern Ng; Mohd Hanif Zulfakar; Syed Maaz Nadeem (Drug Delivery and Translational Research, 2019)

Chemogenic silver nanoparticles enhance lignans and neolignans in cell suspension cultures of Linum usitatissimum L. - Adnan Zahir; Muhammad Nadeem; Waqar Ahmad; Nathalie Giglioli-Guivarc’h; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Interactive Effects of Genotype and Nitrogen on the Phenology and Yield Determination of Okra [Abelmoschus esculentus (L.)] - Saba Fatima; Muhammad Sohail Khan; Muhammad Nadeem; Ilham Khan; Kashif Waseem; Muhammad Nisar; Muhammad Iqbal (International Journal of Plant Production, 2019)

Proline-mediated changes in antioxidant enzymatic activities and the physiology of sugar beet under drought stress - Hamideh Ghaffari; Mahmoud Reza Tadayon; Muhammad Nadeem; Mumtaz Cheema; Jamshid Razmjoo (Acta Physiologiae Plantarum, 2019)

Yeast-extract improved biosynthesis of lignans and neolignans in cell suspension cultures of Linum usitatissimum L. - Muhammad Nadeem; Bilal Haider Abbasi; Laurine Garros; Samantha Drouet; Adnan Zahir; Waqar Ahmad; Nathalie Giglioli-Guivarc’h; Christophe Hano (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Simultaneously Improving Mechanical, Formulation, and In Vivo Performance of Naproxen by Co-Crystallization - Nasir Abbas; Sumera Latif; Hafsa Afzal; Muhammad Sohail Arshad; Amjad Hussain; Saleha Sadeeqa; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2018)

Estimation of wind speed using regional frequency analysis based on linear‐moments - Muhammad Fawad; Ishfaq Ahmad; Falaq Ali Nadeem; Ting Yan; Aamar Abbas (International Journal of Climatology, 2018)
The quantiles of annual maximum wind speed (AMWS) can be estimated for different meteorological stations of interest by using at‐site frequency analysis and extreme value theory. These estimates are of immense importance for the codification of wind speed. However, the historical data of wind speed at the number of meteorological stations are sometimes unavailable and often insufficient due to the shorter length, especially in developing countries like Pakistan. The scarcity of the data increases the uncertainty of the quantiles estimates regarding policy implications. To cope with the problem, an approach of Regional Frequency Analysis (RFA) is opted here. In this study, RFA of AMWS using linear‐moments (L‐moments) is carried out by considering wind speed data of nine meteorological stations of province Punjab, Pakistan. No station is found to be discordant. A single homogenous region is constituted from these nine stations using a subjective approach based on their geographical locations. Heterogeneity measures justify that these nine stations of Punjab form a single homogeneous region. Regional quantiles estimates are found through the most appropriate probability distribution among generalized normal (GNO), generalized logistic (GLO), Pearson Type 3 (P3), generalized Pareto (GPA), Weibull (WEI), log Pearson Type 3 (LP3) and generalized extreme value (GEV) distributions. Z ‐statistic and L‐moment ratio diagram suggest that GLO and GNO distributions are better choices than others. Robustness of both distributions is evaluated through relative bias (RB) and relative root mean square error (RRMSE). Findings indicate that overall, GLO distribution is better than GNO. Further, we also find at‐site quantiles from dimensionless quantities (regional quantiles) using the sample mean and median as scaling factors. Quantiles' estimates calculated from this study can be used in codified structural designs for policy implications.

Impact of maturity on phenolic composition and antioxidant activity of medicinally important leaves of Ficus carica L. - Muhammad Nadeem; Alam Zeb (Physiology and Molecular Biology of Plants, 2018)

Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability - Regie Lyn P. Santos-Cortez; Valeed Khan; Falak Sher Khan; Zaib-un-Nisa Mughal; Imen Chakchouk; Kwanghyuk Lee; Memoona Rasheed; Rifat Hamza; Anushree Acharya; Ehsan Ullah; Muhammad Arif Nadeem Saqib; Izoduwa Abbe; et al. (Human Genetics, 2018)

Resveratrol as an anti-cancer agent: A review - Abdur Rauf; Muhammad Imran; Masood Sadiq Butt; Muhammad Nadeem; Dennis G. Peters; Mohammad S. Mubarak (Critical Reviews in Food Science and Nutrition, 2018)

Genome-Wide Analysis of Potassium Transport-Related Genes in Chickpea (Cicer arietinum L.) and Their Role in Abiotic Stress Responses - Farrukh Azeem; Bilal Ahmad; Rana Muhammad Atif; Muhammad Amjad Ali; Habibullah Nadeem; Sabir Hussain; Hamid Manzoor; Muhammad Azeem; Muhammad Afzal (Plant Molecular Biology Reporter, 2018)

Cucurmin, anticancer, & antitumor perspectives: A comprehensive review - Muhammad Imran; Azmat Ullah; Farhan Saeed; Muhammad Nadeem; Muhammad Umair Arshad; Hafiz Ansar Rasul Suleria (Critical Reviews in Food Science and Nutrition, 2018)

A novel Salvialactomine from the callus culture of Salvia santolinifolia Boiss - Tour Jan; Raiha Qadri; Beena Naqvi; Achyut Adhikari; Said Nadeem; Akhtar Muhammad (Natural Product Research, 2018)

Osteopontin gene polymorphism association with milk traits and its expression analysis in milk of riverine buffalo - Sidra Manzoor; Asif Nadeem; Javed Maryam; Abu Saeed Hashmi; Muhammad Imran; Masroor Ellahi Babar (Tropical Animal Health and Production, 2018)

Concurrent vaccination of goats with foot and mouth disease (FMD) and peste des petits ruminants (PPR) booster vaccines - Muhammad Khalid Mansoor; Abdullmajeed Hamood Al-Rawahi; Hatim Ali El-Tahir; Badar Al-Faraei; Muhammad Hammad Hussain; Muhammad Nadeem Asi; Ibrahim Al-Hussani; Safwat Sabar (Tropical Animal Health and Production, 2018)

Combined Applications of Aminoethoxyvinylglycine with Salicylic Acid or Nitric Oxide Reduce Oxidative Stress in Peach During Ripening and Cold Storage - Mohammad Javed Tareen; Zora Singh; Ahmad Sattar Khan; Nadeem Akhtar Abbasi; Muhammad Naveed (Journal of Plant Growth Regulation, 2017)

Biology and management of Avena fatua and Avena ludoviciana: two noxious weed species of agro-ecosystems - Ali Ahsan Bajwa; Muhammad Javaid Akhter; Nadeem Iqbal; Arslan Masood Peerzada; Zarka Hanif; Sudheesh Manalil; Saima Hashim; Hafiz Haider Ali; Lynda Kebaso; David Frimpong; Halima Namubiru; Bhagirath Singh Chauhan (Environmental Science and Pollution Research, 2017)

Currently used organophosphate and brominated flame retardants in the environment of China and other developing countries (2000–2016) - Nadeem Ali; Khurram Shahzad; Muhammad Imtiaz Rashid; Heqing Shen; Iqbal Mohammad Ibrahim Ismail; Syed Ali Musstjab Akber Shah Eqani (Environmental Science and Pollution Research, 2017)

Effect of Rheology and Poloxamers Properties on Release of Drugs from Silicon Dioxide Gel-Filled Hard Gelatin Capsules—A Further Enhancement of Viability of Liquid Semisolid Matrix Technology - Misbah Sultana; Mobashar Ahmad Butt; Tariq Saeed; Rizwan Mahmood; Saeed ul Hassan; Khalid Hussain; Syed Atif Raza; Muhammad Ahsan; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2017)

Disaster risk management in agriculture: tragedies of the smallholders - Raza Ullah; Ganesh P. Shivakoti; Farhad Zulfiqar; Muhammad Nadeem Iqbal; Ashfaq Ahmad Shah (Natural Hazards, 2017)

Risk-based framework for optimizing residual chlorine in large water distribution systems - Muhammad Nadeem Sharif; Ashraf Farahat; Husnain Haider; Muhammad A. Al-Zahrani; Manuel J. Rodriguez; Rehan Sadiq (Environmental Monitoring and Assessment, 2017)

Manganese nutrition improves the productivity and grain biofortification of fine grain aromatic rice in conventional and conservation production systems - Aman Ullah; Muhammad Farooq; Asif Nadeem; Abdul Rehman; Saeed A. Asad; Ahmad Nawaz (Paddy and Water Environment, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Plant growth promoting rhizobacteria suppress blast disease caused by Pyricularia oryzae and increase grain yield of rice - Afroz Rais; Muhammad Shakeel; Fauzia Yusuf Hafeez; Muhammad Nadeem Hassan (BioControl, 2016)

Synthesis, in vitro potential and computational studies on 2-amino-1, 4-dihydropyrimidines as multitarget antibacterial ligands - Muhammad Jawad Ahmad; Syed Fahad Hassan; Riffat Un Nisa; Khurshid Ayub; Muhammad Shahid Nadeem; Samina Nazir; Farzana Latif Ansari; Naveeda Akhtar Qureshi; Umer Rashid (Medicinal Chemistry Research, 2016)

First report on fish cysteine as a biomarker of contamination in the River Chenab, Pakistan - Bilal Hussain; Tayyaba Sultana; Salma Sultana; Shahid Mahboob; Muhammad Farooq; Khalid Al-Ghanim; Shahid Nadeem (Environmental Science and Pollution Research, 2016)

Optimization of chlorination boosters in drinking water distribution network for Al-Khobar City in Saudi Arabia - Muhammad Nadeem Sharif; Ashraf Farahat; Muhammad A. Al-Zahrani; Nilufar Islam; Manuel J. Rodriguez; Rehan Sadiq (Arabian Journal of Geosciences, 2016)

Use of RSM modeling for optimizing decolorization of simulated textile wastewater by Pseudomonas aeruginosa strain ZM130 capable of simultaneous removal of reactive dyes and hexavalent chromium - Zahid Maqbool; Sabir Hussain; Tanvir Ahmad; Habibullah Nadeem; Muhammad Imran; Azeem Khalid; Muhammad Abid; Fabrice Martin-Laurent (Environmental Science and Pollution Research, 2016)

Relationship between in vitro characterization and comparative efficacy of plant growth-promoting rhizobacteria for improving cucumber salt tolerance - Sajid Mahmood Nadeem; Maqshoof Ahmad; Muhammad Naveed; Muhammad Imran; Zahir Ahmad Zahir; David E. Crowley (Archives of Microbiology, 2016)

Correlation studies on nitrogen for sunflower crop across the agroclimatic variability - Wajid Nasim; Hatem Belhouchette; Muhammad Tariq; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Mubeen; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary; Imran Khan; Faisal Mahmood; Tauqeer Abbas; Fahd Rasul; et al. (Environmental Science and Pollution Research, 2016)

A case study of Precambrian to Eocene sediments’ hydrocarbon potential assessment in Central Indus Basin of Pakistan - Shazia Asim; Peimin Zhu; Shahid Nadeem Qureshi; Muhammad Tayyab Naseer (Arabian Journal of Geosciences, 2015)

Microwave Assisted Synthesis, Physicochemical, Photophysical, Single Crystal X-ray and DFT Studies of Novel Push–Pull Chromophores - Salman A. Khan; Abdullah M. Asiri; Hadi Mussa Basisi; Muhammad Nadeem Arshad; Kamlesh Sharma (Journal of Fluorescence, 2015)

Suppression of red rot disease by Bacillus sp. based biopesticide formulated in non-sterilized sugarcane filter cake - Muhammad Nadeem Hassan; Namood-e-Sahar; Syed Zia-Ul-Husnain Shah; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2015)

Mutation of ATF6 causes autosomal recessive achromatopsia - Muhammad Ansar; Regie Lyn P. Santos-Cortez; Muhammad Arif Nadeem Saqib; Fareeha Zulfiqar; Kwanghyuk Lee; Naeem Mahmood Ashraf; Ehsan Ullah; Xin Wang; Sundus Sajid; Falak Sher Khan; Muhammad Amin-ud-Din; Joshua D. Smith; et al. (Human Genetics, 2015)

Neuroprotective effect from stem bark extracts of Knema laurina against H 2 O 2 - and Aβ 1–42 -induced cell death in human SH-SY5Y cells - Norsharina Ismail; Muhammad Nadeem Akhtar; Maznah Ismail; Seema Zareen; Syed Adnan Ali Shah; Nordin Hj Lajis; Saiful N. Tajuddin (Natural Product Research, 2015)

Crossability among modern roses and heterosis of quantitative and qualitative traits in hybrids - Muhammad Nadeem; Adnan Younis; Atif Riaz; Ki-Byung Lim (Horticulture, Environment, and Biotechnology, 2015)

Process optimisation for the biosynthesis of cellulase by Bacillus PC-BC6 and its mutant derivative Bacillus N3 using submerged fermentation - Roheena Abdullah; Wajeeha Zafar; Muhammad Nadeem; Mehwish Iqtedar; Shagufta Naz; Quratulain Syed; Afshan Kaleem (Natural Product Research, 2015)

Impact of nanoparticles on human and environment: review of toxicity factors, exposures, control strategies, and future prospects - Muhammad Sajid; Muhammad Ilyas; Chanbasha Basheer; Madiha Tariq; Muhammad Daud; Nadeem Baig; Farrukh Shehzad (Environmental Science and Pollution Research, 2015)

Random mutagenesis and media optimisation for hyperproduction of cellulase from Bacillus species using proximally analysed Saccharum spontaneum in submerged fermentation - Roheena Abdullah; Wajeeha Zafar; Muhammad Nadeem; Mehwish Iqtedar; Shagufta Naz; Quratulain Syed; Zahid Ali Butt (Natural Product Research, 2015)

Effect of alkaline pretreatment on delignification of wheat straw - Umar Asghar; Muhammad Irfan; Mehvish Iram; Zile Huma; Rubina Nelofer; Muhammad Nadeem; Quratulain Syed (Natural Product Research, 2015)

Effect of oxytocin on serum biochemistry, liver enzymes, and metabolic hormones in lactating Nili Ravi buffaloes - Zafar Iqbal; Zia ur Rahman; Faqir Muhammad; Masood Akhtar; Mian Muhammad Awais; Tanweer Khaliq; Amar Nasir; Muhammad Nadeem; Kinza Khan; Hafiz Muhammad Arshad; Muhammad Abdul Basit (Tropical Animal Health and Production, 2015)

Expression line approach to recombinant human epidermal growth factor into the yeast, Pichia pastoris from Huh-7 cell line - Mohsin Ahmad Khan; Faidad Khan; Nadeem Ahmad; Muhammad Islam Khan; Ahmad Usman Zafar; Tayyab Husnain (Molecular Biology Reports, 2014)

Preservation of Bone Structure and Function by Lithothamnion sp. Derived Minerals - Muhammad Nadeem Aslam; Ingrid Bergin; Karl Jepsen; Jaclynn M. Kreider; Kristin H. Graf; Madhav Naik; Steven A. Goldstein; James Varani (Biological Trace Element Research, 2013)

Maize seedling phosphorus nutrition: Allocation of remobilized seed phosphorus reserves and external phosphorus uptake to seedling roots and shoots during early growth stages - Muhammad Nadeem; Alain Mollier; Christian Morel; Muhammad Shahid; Muhammad Aslam; Muhammad Zia-ur-Rehman; Muhammad Ashfaq Wahid; Sylvain Pellerin (Plant and Soil, 2013)

Antioxidant and lipoxygenase inhibiting new iridoid glucosides from Caryopteris odorata - Tayyaba Shahzadi; Muhammad Athar Abbasi; Aziz Ur-Rehman; Tauheeda Riaz; Khalid Mohammed Khan; Muhammad Ashraf; Iftikhar Afzal; Muhammad Nadeem Akhtar; Muhammad Ajaib (Natural Product Research, 2013)

Growth Control in Colon Epithelial Cells: Gadolinium Enhances Calcium-Mediated Growth Regulation - Durga Attili; Brian Jenkins; Muhammad Nadeem Aslam; Michael K. Dame; James Varani (Biological Trace Element Research, 2012)

Maize (Zea mays L.) endogenous seed phosphorus remobilization is not influenced by exogenous phosphorus availability during germination and early growth stages - Muhammad Nadeem; Alain Mollier; Christian Morel; Alain Vives; Loïc Prud’homme; Sylvain Pellerin (Plant and Soil, 2012)

The anti-arthritic and anti-oxidative effect of NBD (6-nitro-1,3-benzodioxane) in adjuvant-induced arthritis (AIA) in rats - Syed Uzair Ali Shah; Nadeem Ashraf; Zahid H. Soomro; Muhammad Raza Shah; Nurul Kabir; Shabana Usman Simjee (Inflammation Research, 2012)

Environmental impact assessment (EIA): an overlooked instrument for sustainable development in Pakistan - Rashid Saeed; Ayesha Sattar; Zafar Iqbal; Muhammad Imran; Raziya Nadeem (Environmental Monitoring and Assessment, 2012)

Assessment of background levels of trace metals in water and soil from a remote region of Himalaya - Munir H. Shah; Javed Iqbal; Nazia Shaheen; Nadeem Khan; Muhammad Aziz Choudhary; Gulraiz Akhter (Environmental Monitoring and Assessment, 2012)

Spatial and temporal characterization of trace elements and nutrients in the Rawal Lake Reservoir, Pakistan using multivariate analysis techniques - Riffat Naseem Malik; Muhammad Nadeem (Environmental Geochemistry and Health, 2011)

Fibroblast Response to Lanthanoid Metal Ion Stimulation: Potential Contribution to Fibrotic Tissue Injury - William Jenkins; Patricia Perone; Kyle Walker; Narasimharao Bhagavathula; Muhammad Nadeem Aslam; Marissa DaSilva; Michael K. Dame; James Varani (Biological Trace Element Research, 2011)

First cloning and characterization of aspartate aminotransferase from river buffalo (Bubalus bubalis) - Muhammad Shahid Nadeem; Naeem Rashid; Muzaffar Iqbal; Qurra-tul-Ann Afza Gardner; Muhammad Akhtar (Biologia, 2011)

Food habits of the snow leopard Panthera uncia (Schreber, 1775) in Baltistan, Northern Pakistan - Muhammad Bilal Anwar; Rodney Jackson; Muhammad Sajid Nadeem; Jan E. Janečka; Shafqat Hussain; Mirza Azhar Beg; Ghulam Muhammad; Mazhar Qayyum (European Journal of Wildlife Research, 2011)

Relative contribution of seed phosphorus reserves and exogenous phosphorus uptake to maize (Zea mays L.) nutrition during early growth stages - Muhammad Nadeem; Alain Mollier; Christian Morel; Alain Vives; Loïc Prud’homme; Sylvain Pellerin (Plant and Soil, 2011)

Erratum to: Hotspots Assessment of Spatial Water Losses in the Off-Farm Open Channels Irrigation Supply System - Muhammad Nadeem Asghar; Mahmood Ali Khan; Bryson Lashbrook; Timo Zumkley; Scott Lawson (Water Resources Management, 2011)

Hotspots Assessment of Spatial Water Losses in the Off-Farm Open Channels Irrigation Supply System - Muhammad Nadeem Asghar; Mahmood Ali Khan; Bryson Lashbrook; Timo Zumkley; Scott Lawson (Water Resources Management, 2011)

Synthesis of a New Tri-Branched PEG-IFNα2 and Its Impact on Anti Viral Bioactivity - Muhammad Farooq Sabar; Mustansara Yaqub; Mohsin Ahmad Khan; Nadeem Ahmad; Muhammad Usman Ghani; Mariam Shahid (International Journal of Peptide Research and Therapeutics, 2010)

Erratum to: Suppression of red rot caused by Colletotrichum falcatum on sugarcane plants using plant growth-promoting rhizobacteria - Muhammad Nadeem Hassan; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2010)

Suppression of red rot caused by Colletotrichum falcatum on sugarcane plants using plant growth-promoting rhizobacteria - Muhammad Nadeem Hassan; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2010)

Evaluation of a 3% surf solution (surf field mastitis test) for the diagnosis of subclinical bovine and bubaline mastitis - Ghulam Muhammad; Abeera Naureen; Muhammad Nadeem Asi; Muhammad Saqib; Fazal-ur-Rehman (Tropical Animal Health and Production, 2010)

Human colon tissue in organ culture: preservation of normal and neoplastic characteristics - Michael K. Dame; Narasimharao Bhagavathula; Cohra Mankey; Marissa DaSilva; Tejaswi Paruchuri; Muhammad Nadeem Aslam; James Varani (In Vitro Cellular & Developmental Biology - Animal, 2010)

Comparative effectiveness of Pseudomonas and Serratia sp. containing ACC-deaminase for improving growth and yield of wheat (Triticum aestivum L.) under salt-stressed conditions - Zahir Ahmad Zahir; Usman Ghani; Muhammad Naveed; Sajid Mahmood Nadeem; Hafiz Naeem Asghar (Archives of Microbiology, 2009)

Cladosporium sphaerospermum as a new plant growth-promoting endophyte from the roots of Glycine max (L.) Merr. - Muhammad Hamayun; Sumera Afzal Khan; Nadeem Ahmad; Dong-Sheng Tang; Sang-Mo Kang; Chae-In Na; Eun-Young Sohn; Young-Hyun Hwang; Dong-Hyun Shin; Byung-Hyun Lee; Jong-Guk Kim; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2009)

Removal of Nickel onto Alkali Treated Rice Bran - Muhammad Nadeem Zafar; Imran Abbas; Raziya Nadeem; Munir Ahmad Sheikh; Muhammad Afzal Ghauri (Water, Air, & Soil Pollution, 2009)

Expression and identification of folate-sensitive fragile sites in British Suffolk sheep (Ovis aries) - Ahmad Ali; Muhammad Abdullah; Masroor Ellahi Babar; Khalid Javed; Asif Nadeem (Journal of Genetics, 2008)

Biosorption of Chromium (III) and Chromium (VI) by Untreated and Pretreated Cassia fistula Biomass from Aqueous Solutions - Mazhar Abbas; Raziya Nadeem; Muhammad Nadeem Zafar; Mamoona Arshad (Water, Air, & Soil Pollution, 2008)

Modeling the impact of groundwater harvesting on the hydro-salinity of a saline catchment in southeastern Australia - Shahbaz Khan; Muhammad Nadeem Asghar; Tariq Rana (Hydrogeology Journal, 2008)

Characterizing Groundwater Dynamics Based on Impact of Pulp and Paper Mill Effluent Irrigation and Climate Variability - Shahbaz Khan; Muhammad Nadeem Asghar; Tariq Rana (Water, Air, & Soil Pollution, 2007)